Long-term impact of 3-D urban expansion on the thermal environment in the Yangtze River Delta region, China - Chenglong Yin; Ruishan Chen; Xiangming Xiao; Yi Yin; Tim Van de Voorde; Yinshuai Li; Nan Jia; Hong Wei; Li Pan; Fei Meng; Yanbin Chen; Bo Xiong; et al. (Land Use Policy, 2026)

Gut microbiota and metabolic profiles alteration during in vitro fecal fermentation of an immunostimulatory polysaccharide from Astragalus membranaceus - Lu Xu; Kailin Li; Tim-Fat Shum; Qianru Lin; Kelvin Sze-Yim Cai; Franco King-Chi Leung; Cheng Li; Jiachi Chiou (Food Research International, 2026)

Transboundary ecosystem service flows in Central Asia: Enhancing global sustainable development goals (SDGs) through the grain–water-carbon-culture network (GWCCN) - Jiangyue Li; Philippe De Maeyer; Tim Van de Voorde; Xi Chen; Yaoming Li (Land Use Policy, 2026)

Emeishan basalt’s contribution to heavy metals in topsoil (notably cadmium) in Southwest China from soil geochemistry evidence - Fang Yang; Liang Tang; Yang Li; Bo Cheng; Tim T. Werner; Lingfei Qu; Ke Cheng; Aiming Zhang; Junbo Wang; Guikai Li (Acta Geochimica, 2026)

Conceptualising and mapping polarisation trends in land systems - Christian Levers; Julian Helfenstein; Matthias Bürgi; Niels Debonne; Vasco Diogo; Rebekka Dossche; Felix Herzog; Yafei Li; Franziska Mohr; Rebecca Swart; Tim G. Williams; Peter H. Verburg (Ambio, 2026)
Polarisation is a key process in land systems, describing land-change trajectories within a region that simultaneously move in opposite directions, such as co-occurring agricultural intensification and abandonment. Land-system polarisation relates strongly to sustainability goals, with potentially positive or negative consequences depending on domain and context. Yet, we lack approaches for mapping polarisation, limiting our understanding of its spatiotemporal distribution and integration into policy or impact assessments. We address this gap by exploring the concept of land-system polarisation and identifying five key dimensions for its mapping: spatial scales, temporal scales, land-use sectors, indicators, and neighbourhood relationships. We propose and test a workflow using the EU’s crop production systems, showing that ~ 87% of NUTS2 regions display polarisation. Our transferable workflow is adaptable across scales and contexts, enabling polarisation to serve as a lens for examining land-change drivers and impacts and providing spatially explicit information to guide targeted intervention and monitoring efforts.

Building soil organic matter differing in physical fractions for fertilizer nitrogen retention - Quan Tang; Qingde Li; Xiaozhi Wang; Yuanyuan Huang; Tim J. Daniell; Enxuan Wu; Jing Wang; Feiyi Zhang; Zhenwang Li; Scott X. Chang; Zucong Cai; Yves Uwiragiye; et al. (Soil Biology and Biochemistry, 2026)

Advancing weather index insurance for climate risk management: A review of modelling techniques and implementation strategies - Charles Joseph; Qingxia Jenny Wang; Shahbaz Mushtaq; Yan Li; Jonathan Barratt; Tim Barratt (Environmental Impact Assessment Review, 2026)

Billboard effects on idealized ground-heated street canyon ventilation across varied wind directions - Daniel Ziyue Peng; Bingchao Zhang; Tim K.T. Tse; Qingshan Yang; Cruz Y. Li (Building and Environment, 2026)

Distinctive Routes for Multi-Year La Niña Formation - Borui Chen; Tim Li; Xiao Pan; Jia Liu (Advances in Atmospheric Sciences, 2026)

Neoarchean ultrahigh-temperature metamorphism in the Saglek–Hebron Complex, northern Labrador - Meiyun Huang; Shujuan Jiao; Tim E. Johnson; Jonathan O’Neil; Hanika Rizo; Chris Clark; Zhongwu Lan; Qiuli Li; Jinghui Guo (Precambrian Research, 2026)

Solar-thermal membrane distillation: Opportunities and challenges - Julianne Rolf; John Floyd; Tim Chomiak; Ze He; Ruikun Xin; Naomi Fuentes; Kuichang Zuo; Jingbo Wang; Omar Alrehaili; Rayan Alghanayem; Moustafa M. Abo El-Fadl; Mohamed A. El-Naggar; et al. (Desalination, 2026)

Corner-billboard windcatcher retrofit for cross-street ventilation in high-density city grids - Bingchao Zhang; Cruz Y. Li; Tim K.T. Tse (Building and Environment, 2026)

Impact of mid-high-latitude Eurasian ISO on extreme hot days in the middle-lower reaches of the Yangtze River valley during boreal summer - Meiling Zhang; Shuangyan Yang; Zhiwei Zhu; Tim Li (Climate Dynamics, 2026)

Sources and transportation of mining metals to soil: A case study from the Lala mining area, Southwest China - Fang Yang; Lei Xu; Liang Tang; Li Dai; Xuemin Liu; Tim T. Werner; Lingfei Qu; Xuefeng Liao; Yang Li; Junbo Wang (Acta Geochimica, 2026)

Deep learning the droughts: Spatiotemporal monitoring of protracted dry conditions in Queensland, Australia - Charles Joseph; Qingxia (Jenny) Wang; Shahbaz Mushtaq; Yan Li; Jonathan Barratt; Tim Barratt (Science of The Total Environment, 2026)

Seasonal prediction of extreme high temperature days in western North America: a comparison of physics-based and machine learning models - Hui Tan; Zhiwei Zhu; Tim Li; Bin Wang (Climate Dynamics, 2026)

Hydrogen injection in blast furnaces: Effects of hydrogen injection temperature under various injection conditions - Jing Li; Shibo Kuang; Tim Evans; Sunny Song; Aibing Yu (Fuel, 2026)

Yeast based N-demethylation for the production of nororipavine in fed-batch or continuous cultivation - Siyi Xue; Xu Li; Daniel Yaw; Tim A. Bowser; Ângela Carvalho; Jørgen Hansen; Sally L. Gras (Bioresource Technology, 2026)

Contribution of dissolved organic carbon to total alkalinity in Enhanced Weathering experiments - Lukas Rieder; Mathilde Hagens; Reinaldy Poetra; Alix Vidal; Tullia Calogiuri; Anna Neubeck; Abhijeet Singh; Thomas Corbett; Harun Niron; Sara Vicca; Siegfried E. Vlaeminck; Iris Janssens; et al. (Applied Geochemistry, 2026)

Geographic origin and post-invasion genetic divergence of Mytilus galloprovincialis in China - Jian'an Li; Ben Yang; Ahmed Mokrani; Mengmeng Xu; Xiaojie Han; Tim P. Bean; Robert P. Ellis; Shikai Liu (Marine Pollution Bulletin, 2026)

The potential of variable-rate technology for sustainable intensification of European arable farming - Yafei Li; Jeanine Ammann; Julian Helfenstein; Tim G. Williams; Christian Levers; Franziska Mohr; Vasco Diogo; Rigas Zafeiriou; Víctor Rolo; Michael Beckmann; Józef Hernik; Thanasis Kizos; et al. (European Journal of Agronomy, 2026)

A novel dual-threshold assessment method for formulating land degradation neutrality priority governance strategies in Central Asia under SDG 15.3.1 - Jiangyue Li; Philippe De Maeyer; Xi Chen; Tim Van de Voorde; Yaoming Li (Environmental Impact Assessment Review, 2026)

Divergent regulation of cellular cholesterol metabolism by seaweed-derived fucosterol and saringosterol - Na Zhan; Nikita Martens; Yanlin Li; Gardi Voortman; Frank Leijten; Silvia Friedrichs; Martien P. M. Caspers; Lars Verschuren; Tim Vanmierlo; Marieke Smit; Folkert Kuipers; Johan W. Jonker; et al. (Frontiers in Marine Science, 2025)
Marine sterols from brown seaweeds, particularly fucosterol and its oxidized derivative saringosterol, have shown therapeutic potential for Alzheimer’s disease (AD) and cardiovascular diseases. Here, we aimed to elucidate the cellular and in vivo mechanisms underlying their beneficial effects. In human HepG2 hepatocytes and CCF-STTG1 astrocytoma cells, we assessed liver x receptor (LXRα /LXRβ) activation, sterol uptake, and effects on cholesterol metabolism using luciferase reporter assays, GC–MS sterol profiling, and 13 C-acetate incorporation. In THP-1–derived macrophages, we evaluated sterol-induced cholesterol efflux using radiolabeled [ 3 H]-cholesterol assays and characterized anti-inflammatory responses by quantifying lipopolysaccharide (LPS) -induced cytokine production. Wild-type C57BL/6J mice were fed diets enriched with either fucosterol (0.2% w/w) or saringosterol (0.02% w/w) for 7 days, after which sterol profiles in serum, liver, and brain were quantified by GC–MS. Hippocampal transcriptional responses were assessed by RNA sequencing. Both fucosterol and saringosterol were internalized by HepG2 and CCF-STTG1 cells and activated LXRα/β, but elicited distinct metabolic effects: fucosterol increased cholesterol synthesis and intracellular desmosterol, whereas saringosterol reduced both; only saringosterol suppressed LPS-induced interleukin (IL)-6 and tumor necrosis factor (TNF)-α production in macrophages, while both enhanced cholesterol efflux. In vivo , fucosterol somewhat elevated hepatic desmosterol and decreased 5α-cholestanol and circulating oxysterols, whereas saringosterol also increased hepatic desmosterol and elevated 7α-hydroxycholesterol in liver and brain as well as serum 27-hydroxycholesterol. Transcriptome analysis revealed that fucosterol primarily modulated synaptic signaling and hormonal pathways linked to neuronal plasticity, while saringosterol affected protein quality control and neurodegenerative pathways. These data are the first on the direct comparison of the cellular and in vivo effects of fucosterol and saringosterol, revealing shared LXR activation but divergent impacts on hepatic, brain and systemic cholesterol metabolism and expression of genes involved in neural pathways, indicating complementary neuroprotective effects with therapeutic potential for AD and related disorders.

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

Corrigendum to “Advanced aspects of acetogens” [Bioresour. Technol. 427 (2025) 131913] - Anja Poehlein; Benjamin Zeldes; Maximilian Flaiz; Tim Böer; Alina Lüschen; Franziska Höfele; Kira S. Baur; Bastian Molitor; Christian Kröly; Meng Wang; Quan Zhang; Yixuan Fan; et al. (Bioresource Technology, 2025)

Identification and SAR studies of indole-functionalized polyamines as antibiotic enhancers - Melissa M. Cadelis; Steven A. Li; Kenneth Sue; Tim Liu; Marie-Lise Bourguet-Kondracki; Marine Blanchet; Jean-Michel Brunel; Brent R. Copp (Phytochemistry Letters, 2025)

Imaging viscosity after the 2021 Mw 7.4 Maduo earthquake: Insights on the regional rheology variation beneath the Bayan Har block - Zhen Li; Wei Xiong; Andrew Hooper; Zeyan Zhao; Yuan Gao; John R. Elliott; Tim J. Wright; Han Yue; Teng Wang (Earth and Planetary Science Letters, 2025)

Integrated multifunctional liquid metal enhanced hydrogel system for chronic infected wound with sinus tract treatment and monitoring - Chengxin Ruan; Jinxue Zhao; Jiale Jin; Dongdong Li; Dongyu Wang; Zhiyuan Luo; Peiyi Li; Apoorva Sinha; Tim-yun Michael Ong; Lidong Wu; Pengfei Lei (Chemical Engineering Journal, 2025)

Origins of synoptic and intraseasonal variabilities in the Northwestern Pacific monsoon trough - Hongyu Chen; Chi Qin; Tim Li (Climate Dynamics, 2025)

The patterns of the Populus euphratica forest and cropland changes upstream of the Tarim River under the policy-driven human activities during 1960–2023 - Haoyu Wang; Junli Li; Yingming Ke; Yihan Zhang; Chenghu Zhou; Chunxia Wei; Zhanfeng Shen; Philippe De Maeyer; Tim Van de Voorde (International Journal of Remote Sensing, 2025)

Advanced aspects of acetogens - Anja Poehlein; Benjamin Zeldes; Maximilian Flaiz; Tim Böer; Alina Lüschen; Franziska Höfele; Kira S. Baur; Bastian Molitor; Christian Kröly; Meng Wang; Quan Zhang; Yixuan Fan; et al. (Bioresource Technology, 2025)

Effect of fetch on street canyon flow field and pollutant dispersion - Daniel Ziyue Peng; Bingchao Zhang; Yunfei Fu; Xisheng Lin; Wenke Li; Tim K.T. Tse; Cruz Y. Li (Building and Environment, 2025)

Global Fire Emissions Linked to Madden-Julian Oscillation - Young-Min Yang; Doo Young Lee; Jae-Heung Park; June-Yi Lee; Kyung-Sook Yun; Soon-Il An; Tim Li; Bin Wang (Advances in Atmospheric Sciences, 2025)
Understanding the relationship between fire activity and climate variability is a major concern for the scientific community and is essential for reducing economic losses and life-threatening fire hazards. However, the drivers of fire activity and the influence of climate variability remain uncertain. Here, we show that the Madden-Julian Oscillation (MJO)—a dominant tropical subseasonal variability—influences fire activity by modulating local fire-supporting weather through atmospheric teleconnections. Our results show that midlatitude fire emissions exhibit significant subseasonal variability, with MJO-related weather influencing the fire intensity and contributing to large fire events. MJO-related fire events account for about 10%–20% of total midlatitude fire events, suggesting that if MJO teleconnections strengthen in the future, fire emissions and associated economic losses could worsen.

Agroecological and technological practices in European arable farming: Past uptake and expert visions for future development - Yafei Li; Julian Helfenstein; Rebecca Swart; Christian Levers; Franziska Mohr; Vasco Diogo; Matthias Bürgi; Tim G. Williams; Rigas Zafeiriou; Anita Zarina; Jeanine Ammann; Víctor Rolo; et al. (Land Use Policy, 2025)

Interannual variations of persistent extreme cold events in northeastern China - Ming Yang; Tim Li; Qingjiu Gao (Climate Dynamics, 2025)

An automatic classification method with weak supervision for large-scale wetland mapping in transboundary (Irtysh River) basin using Sentinel 1/2 imageries - Kaiyue Luo; Alim Samat; Tim Van de voorde; Weiguo Jiang; Wenbo Li; Jilili Abuduwaili (Journal of Environmental Management, 2025)

Causes of Winter Persistent Extreme Cold Events in Northeastern China - Ming Yang; Qingjiu Gao; Tim Li (Advances in Atmospheric Sciences, 2025)

Why zonal wind anomalies were “decoupled” to El Niño in July 2023 - Yuhang Zhao; Tim Li; Xiao Pan (Climate Dynamics, 2025)

Influence of northward-propagating intraseasonal oscillations and ENSO background states on summer monsoon onset over the Arabian Sea and India - Tsung-Hsun Lin; Mong-Ming Lu; Tim Li (Climate Dynamics, 2025)

Crystallinity and dissolution-recrystallization mechanism controlled As(V) retention by calcium phosphate - Yao Yan; Xun Cao; Jun Li; Hanxiao Zhang; Yongqiang Yang; Fanrong Chen; Runliang Zhu; Dong Liu; Tim White; Shijun Wu (Journal of Hazardous Materials, 2025)

Emitted droplets and aerosols and their transmission when drying hands under an air-jet dryer - Zilong Gao; Yuguo Li; Feng Wang; Lin Duanmu; Tengfei (Tim) Zhang (Journal of Hazardous Materials, 2025)

A novel life-cycle analysis framework to assess the performances of tall buildings considering the climate change - Jiayao Wang; Siqi Cao; Tim K.T. Tse; Sunwei Li; Jimmy C.H. Fung; Yutong Li (Engineering Structures, 2025)

Correction to: Patterns and determinants of microbial- and plant-derived carbon contributions to soil organic carbon in tea plantation chronosequence - Quan Tang; Wei Li; Wenxia Dai; Jing Wang; Feiyi Zhang; Tim J. Daniell; Yi Cheng; Shengsen Wang; Weiqin Yin; Xiaozhi Wang (Plant and Soil, 2024)

Patterns and determinants of microbial- and plant-derived carbon contributions to soil organic carbon in tea plantation chronosequence - Quan Tang; Wei Li; Wenxia Dai; Jing Wang; Feiyi Zhang; Tim J. Daniell; Yi Cheng; Shengsen Wang; Weiqin Yin; Xiaozhi Wang (Plant and Soil, 2024)

Towards a Climate Service for the Tea Industry: A Collaborative Approach between the UK and China - Stacey New; Shaojuan Li; Tongwen Zhao; Elisabeth Thompson; Nicola Bown; Tim Mitchell; Amy Waterson; Jennifer H. Weeks; Jing Yang; Rosie Oakes; Tianjun Zhou; Nicola Golding (Advances in Atmospheric Sciences, 2024)

Advancing Our Understanding of Eddy-driven Jet Stream Responses to Climate Change – A Roadmap - Albert Ossó; Ileana Bladé; Alexey Karpechko; Camille Li; Douglas Maraun; Olivia Romppainen-Martius; Len Shaffrey; Aiko Voigt; Tim Woollings; Giuseppe Zappa (Current Climate Change Reports, 2024)
Purpose of Review Extratropical jets and associated storm tracks significantly influence weather and regional climate across various timescales. Understanding jet responses to climate change is essential for reliable regional climate projections. This review serves two main purposes: (1) to provide an accessible overview of extratropical jet dynamics and a comprehensive examination of current challenges and uncertainties in predicting jet responses to greenhouse gas increases and (2) to suggest innovative experiments to advance our understanding of these responses. Recent Findings While successive generations of climate model ensembles consistently project a mean poleward shift of the midlatitude zonal-mean maximum winds, there remains considerable intermodel spread and large uncertainty across seasonal and regional jet responses. Of particular note is our limited understanding of how these jets respond to the intricate interplay of multiple concurrent drivers, such as the strong warming in polar and tropical regions, and the relative importance of each factor. Furthermore, the difficulty of simulating processes requiring high resolution, such as those linked to sharp sea surface temperature gradients or diabatic effects related to tropical convection and extratropical cyclones, has historically hindered progress. Summary We advocate for a collaborative effort to enhance our understanding of the jet stream response to climate change. We propose a series of new experiments that take advantage of recent advances in computing power and modelling capabilities to better resolve small-scale processes such as convective circulations, which we consider essential for a good representation of jet dynamics.

Thirty years of 3-D urbanization in the Yangtze River Delta, China - Chenglong Yin; Ruishan Chen; Xiangming Xiao; Tim Van de Voorde; Yuanwei Qin; Xiaona Guo; Fei Meng; Li Pan; Yuan Yao; Yinshuai Li (Science of The Total Environment, 2024)

A review on power control of wind turbines with the perspective of dynamic load mitigation - Jiayao Wang; Farshad Golnary; Sunwei Li; Asiri Umenga Weerasuriya; Kam Tim Tse (Ocean Engineering, 2024)

An overview of cellulose aerogels and foams for oil sorption: Preparation, modification, and potential of 3D printing - Ang Li; Tim Huber; David Barker; Ali Reza Nazmi; Hossein Najaf Zadeh (Carbohydrate Polymers, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Pedestrian-level wind environment surrounding two tandem non-identical height elevated buildings under the influence of twisted wind flows - Wenxin Li; Cheuk Ming Mak; Yunfei Fu; Chenzhi Cai; Kam Tim Tse; Jianlei Niu; Sam Ho Yan Wong (Sustainable Cities and Society, 2024)

Koopman mode analysis on discovering distributed energy transfer of post-transient flutter of a bluff body - Qingchi Zhu; Hao Li; Hao Zhu; Lei Zhou; Kam Tim Tse; Hongfu Zhang (Ocean Engineering, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Globally assessing how evapotranspiration feedbacks govern the impacts of multi-year droughts - Qiang Liu; Liqiao Liang; Tim R. McVicar; Xuan Wang; Chunhui Li; Xinghui Xia; Denghua Yan (Journal of Hydrology, 2024)

Sustainable urban road planning under the digital twin-MCDM-GIS framework considering multidisciplinary factors - Feng Jiang; Junda Li; Ling Ma; Zejiao Dong; Weiwei Chen; Tim Broyd; Guohao Wang (Journal of Cleaner Production, 2024)

Southward-shift zonal wind patterns during ENSO in CMIP6 models - Yuhan Gong; Tim Li (Climate Dynamics, 2024)

Measurement and prediction of the detachment of Aspergillus niger spores in turbulent flows - Tengfei (Tim) Zhang; Nuo Li; Xinzi Xu; Nan Jiang; Mengqiang Lv (Journal of Hazardous Materials, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Tropical or extratropical cyclones: what drives the compound flood hazard, impact, and risk for the United States Southeast Atlantic coast? - Kees Nederhoff; Tim W. B. Leijnse; Kai Parker; Jennifer Thomas; Andrea O’Neill; Maarten van Ormondt; Robert McCall; Li Erikson; Patrick L. Barnard; Amy Foxgrover; Wouter Klessens; Norberto C. Nadal-Caraballo; et al. (Natural Hazards, 2024)
Subtropical coastlines are impacted by both tropical and extratropical cyclones. While both may lead to substantial damage to coastal communities, it is difficult to determine the contribution of tropical cyclones to coastal flooding relative to that of extratropical cyclones. We conduct a large-scale flood hazard and impact assessment across the subtropical Southeast Atlantic Coast of the United States, from Virginia to Florida, including different flood hazards. The physics-based hydrodynamic modeling skillfully reproduces coastal water levels based on a comprehensive validation of tides, almost two hundred historical storms, and an in-depth hindcast of Hurricane Florence. We show that yearly flood impacts are two times as likely to be driven by extratropical than tropical cyclones. On the other hand, tropical cyclones are 30 times more likely to affect people during rarer 100-year events than extratropical cyclones and contribute to more than half of the regional flood risk. With increasing sea levels, more areas will be flooded, regardless of whether flooding is driven by tropical or extratropical cyclones. Most of the absolute flood risk is contained in the greater Miami metropolitan area. However, several less populous counties have the highest relative risks. The results of this study provide critical information for understanding the source and frequency of compound flooding across the Southeast Atlantic Coast of the United States.

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Correction: Formation of long-lasting inactive and active multiple tropical cyclone events in the western North Pacific - Lilan Chen; Jianyun Gao; Tim Li (Climate Dynamics, 2024)

Biochar is colonized by select arbuscular mycorrhizal fungi in agricultural soils - Patrick Neuberger; Carlos Romero; Keunbae Kim; Xiying Hao; Tim A. McAllister; Skyler Ngo; Chunli Li; Monika A. Gorzelak (Mycorrhiza, 2024)
Arbuscular mycorrhizal fungi (AMF) colonize biochar in soils, yet the processes governing their colonization and growth in biochar are not well characterized. Biochar amendment improves soil health by increasing soil carbon, decreasing bulk density, and improving soil water retention, all of which can increase yield and alleviate environmental stress on crops. Biochar is often applied with nutrient addition, impacting mycorrhizal communities. To understand how mycorrhizas explore soils containing biochar, we buried packets of non-activated biochar in root exclusion mesh bags in contrasting agricultural soils. In this greenhouse experiment, with quinoa ( Chenopodium quinoa ) as the host plant, we tested impacts of mineral nutrient (as manure and fertilizer) and biochar addition on mycorrhizal colonization of biochar. Paraglomus appeared to dominate the biochar packets, and the community of AMF found in the biochar was a subset (12 of 18) of the virtual taxa detected in soil communities. We saw differences in AMF community composition between soils with different edaphic properties, and while nutrient addition shifted those communities, the shifts were inconsistent between soil types and did not significantly influence the observation that Paraglomus appeared to selectively colonize biochar. This observation may reflect differences in AMF traits, with Paraglomus previously identified only in soils (not in roots) pointing to predominately soil exploratory traits. Conversely, the absence of some AMF from the biochar implies either a reduced tendency to explore soils or an ability to avoid recalcitrant nutrient sources. Our results point to a selective colonization of biochar in agricultural soils.

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Wind tunnel measurement of pedestrian-level gust wind flow and comfort around irregular lift-up buildings within simplified urban arrays - Wenxin Li; Cheuk Ming Mak; Chenzhi Cai; Yunfei Fu; Kam Tim Tse; Jianlei Niu (Building and Environment, 2024)

Environmental and economic spatial analysis system for biochar production – Case studies in the East of England and the East Midlands - Yuzhou Tang; Yue Li; Tim T. Cockerill (Biomass and Bioenergy, 2024)

Formation of long-lasting inactive and active multiple tropical cyclone events in the western North Pacific - Lilan Chen; Jianyun Gao; Tim Li (Climate Dynamics, 2024)

Seasonal climate forecast-an important tool in managing the risk of extreme weather events in Australia's wheat industry - Qunying Luo; Li Wen; Tim Cowan; Dale Schilling (Agricultural and Forest Meteorology, 2024)

Advancing botanical safety: A strategy for selecting, sourcing, and characterizing botanicals for developing toxicological tools - Suramya Waidyanatha; Bradley J. Collins; Tim Cristy; Michelle Embry; Stefan Gafner; Holly Johnson; Josh Kellogg; Julie Krzykwa; Siheng Li; Constance A. Mitchell; Esra Mutlu; Sarah Pickett; et al. (Food and Chemical Toxicology, 2024)

Smart urban windcatcher: Conception of an AI-empowered wind-channeling system for real-time enhancement of urban wind environment - Bingchao Zhang; Cruz Y. Li; Hideki Kikumoto; Jianlei Niu; Tim K.T. Tse (Building and Environment, 2024)

A scalable biomanufacturing platform for bacterial magnetosomes - Alfred Fernández-Castané; Hong Li; Moritz Ebeler; Matthias Franzreb; Tim W. Overton; Owen R.T. Thomas (Food and Bioproducts Processing, 2024)

Modification of grilles to improve the lavatory environment on an aircraft - Tengfei (Tim) Zhang; Pin Li; Chao-Hsin Lin; Feng Wang (Building and Environment, 2024)

Distinctive changes of Asian–African summer monsoon in interglacial epochs and global warming scenario - Yuhao Wang; Chao He; Tim Li; Chengming Zhang; Xiaoli Gu (Climate Dynamics, 2024)

Ecological security warning in Central Asia: Integrating ecosystem services protection under SSPs-RCPs scenarios - Jiangyue Li; Xi Chen; Philippe De Maeyer; Tim Van de Voorde; Yaoming Li (Science of The Total Environment, 2024)

Coastal eutrophication driven by long-distance transport of large river nutrient loads, the case of Xiangshan Bay, China - Xiangyu Sun; Jingjing Zhang; Hongliang Li; Yong Zhu; Xingju He; Yibo Liao; Zhibing Jiang; Lu Shou; Zhiwen Wang; Tim C. Jennerjahn; Jianfang Chen (Science of The Total Environment, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Integrated analysis of the transport process and source attribution of an extreme ozone pollution event in Hefei at different vertical heights: A case of study - Feng Hu; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Aurelia Lupaşcu; Tim Butler; Zhaokun Hu; YinSheng Lv; ZhiDong Zhang; Jiangyi Zheng (Science of The Total Environment, 2024)

Copper oxide particle emission and the spread in a public washroom from a high-speed jet air dryer - Zilong Gao; Yuguo Li; Lin Duanmu; Tengfei (Tim) Zhang (Journal of Hazardous Materials, 2024)

Why is the Pacific meridional mode most pronounced in boreal spring? - Zilu Meng; Tim Li (Climate Dynamics, 2024)

Sensitivity of the Size of a TC to Sea Surface Temperatures in Its Outer Region - Mingyu Bi; Tim Li (Journal of Meteorological Research, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The magnesium isotopic composition of the mantle - Xiao-Ning Liu; Remco C. Hin; Christopher D. Coath; Michael Bizimis; Li Su; Dmitri A. Ionov; Eiichi Takazawa; Richard Brooker; Tim Elliott (Geochimica et Cosmochimica Acta, 2023)

To what extent does ENSO rectify the tropical Pacific mean state? - Manrui Xue; Tim Li (Climate Dynamics, 2023)

Characteristics of diurnal condensational heating at the Western Maritime Continent during MJO eastward propagation - Yan Zhu; Tim Li (Climate Dynamics, 2023)

Energy savings and thermal comfort in a zero energy office building with fans in Singapore - Michael G. Kent; Nam Khoa Huynh; Asit Kumar Mishra; Federico Tartarini; Aleksandra Lipczynska; Jiayu Li; Zurami Sultan; Edwin Goh; Giridharan Karunagaran; Arulmani Natarajan; Asiri Indrajith; Ivanna Hendri; et al. (Building and Environment, 2023)

Precipitation diurnal cycle over the maritime continent modulated by ENSO - Jiahao Lu; Tim Li; Xinyong Shen (Climate Dynamics, 2023)

Influence of boreal summer intraseasonal oscillation on summer precipitation in North China - Lisheng Hao; Tim Li; Lujun Zhang; Ning Ma (International Journal of Climatology, 2023)
To understand the impact of the boreal summer intraseasonal oscillation (BSISO) propagation on summer precipitation in North China, this study analysed the quantitative relationship between the BSISO and summer precipitation in North China and its influence mechanism using summer precipitation data from 1981 to 2020, the NCEP/NCAR reanalysis data and the NOAA outgoing longwave radiation (OLR). The results show that there is a strong correlation between summer precipitation in North China and the BSISO. Over the past 40 years, the variance in summer precipitation anomalies in North China caused by BSISO1 accounted for 16.8%, whereas the impact of BSISO2 accounted for 13.1%. Their combined impact accounted for 30% of the variance in summer precipitation in North China. The BSISO influences summer precipitation process in North China primarily through upper tropospheric circulation and lower‐level water vapour transport. At 500 and 200 hPa, the BSISO excited some disturbance centres of a deep barotropic structure propagating from west to east along the upper‐tropospheric westerly jet. North China is controlled by the blocking circulation pattern of “high in the east and low in the west” while there is a negative (positive) anomaly near Lake Baikal and a positive (negative) anomaly near the Korean Peninsula. At 850 hPa, the BSISO stimulates an anticyclonic circulation anomaly on the north side of its convective area, and the southerly winds on the west side of the anticyclone enhance water vapour transport to North China. This high‐ and low‐level circulation configuration is favourable for precipitation processes in North China. The results suggest that the influence of both low‐frequency signals in the middle and high latitudes and the BSISO signal in the tropics should be considered to make extended‐range forecasts of precipitation processes in North China.

Holocene variations in the Asian Summer and Winter Monsoons reconstructed from extensive lacustrine sediments in the Mu Us Desert, northern China - Xiaohao Wen; Matt W. Telfer; Baosheng Li; Wei Wang; Tim Daley; Chen Wang; Mengyuan Tian; Mingkun Qiu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Systematic framework for sustainable urban road alignment planning - Feng Jiang; Ling Ma; Tim Broyd; Junda Li; Jing Jia; Hanbin Luo (Transportation Research Part D: Transport and Environment, 2023)

Increased synoptic variability along the subtropical Meiyu front under global warming - Guang Yang; Tim Li (Climate Dynamics, 2023)

Responsibility Under Uncertainty: Which Climate Decisions Matter Most? - Nicola Botta; Nuria Brede; Michel Crucifix; Cezar Ionescu; Patrik Jansson; Zheng Li; Marina Martínez; Tim Richter (Environmental Modeling & Assessment, 2023)
We propose a new method for estimating how much decisions under monadic uncertainty matter. The method is generic and suitable for measuring responsibility in finite horizon sequential decision processes. It fulfills “fairness” requirements and three natural conditions for responsibility measures: agency, avoidance and causal relevance. We apply the method to study how much decisions matter in a stylized greenhouse gas emissions process in which a decision maker repeatedly faces two options: start a “green” transition to a decarbonized society or further delay such a transition. We account for the fact that climate decisions are rarely implemented with certainty and that their consequences on the climate and on the global economy are uncertain. We discover that a “moral” approach towards decision making — doing the right thing even though the probability of success becomes increasingly small — is rational over a wide range of uncertainties.

A novel subgenotype I3 of hepatitis B virus in Guangxi, China: a 15-year follow-up study - Hui-Hua Jia; Qin-Yan Chen; Zhi-Hua Jiang; Xue-Yan Wang; Wen-Jia Zhang; Xiang He; Tim J. Harrison; J. Brooks Jackson; Li Wu; Zhong-Liao Fang (Virus Genes, 2023)

Bi-functional antibody-CRISPR/Cas12a ribonucleoprotein conjugate for improved immunoassay performance - Fei Deng; Yi Li; Tim Hall; Graham Vesey; Ewa M. Goldys (Analytica Chimica Acta, 2023)

Interaction of age and elevation on xylogenesis in Juniperus przewalskii in a cold and arid region - Junzhou Zhang; Xiaohua Gou; Tim Rademacher; Lijuan Wang; Yulin Li; Qipeng Sun; Fang Wang; Zongying Cao (Agricultural and Forest Meteorology, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

Delineation of the complex microbial nitrogen-transformation network in an anammox-driven full-scale wastewater treatment plant - Pengfei Hu; Youfen Qian; Jinye Liu; Lin Gao; Yuxin Li; Yanbin Xu; Jiapeng Wu; Yiguo Hong; Tim Ford; Adi Radian; Yuchun Yang; Ji-Dong Gu (Water Research, 2023)

Three distinct circulation patterns that induce enhanced intraseasonal precipitation events over South China in boreal winter - Lu Wang; Jie Jiang; Tim Li; Xuan Zhou; Ziqi Chen (Climate Dynamics, 2023)

Role of rural built environment in travel mode choice: Evidence from China - Zhao Yu; Peilin Li; Tim Schwanen; Pengjun Zhao; Zhifeng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Phase evolution and arsenic immobilization of arsenate-bearing amorphous calcium phosphate - Yao Yan; Yanan Fang; Vivek Verma; Jun Li; Yong Wang; Yongqiang Yang; Fanrong Chen; Runliang Zhu; Shijun Wu; Thomas J.N. Hooper; Tim White (Journal of Hazardous Materials, 2023)

Demand reduction and energy saving potential of thermal energy storage integrated heat pumps - Jason Hirschey; Zhenning Li; Kyle R. Gluesenkamp; Tim J. LaClair; Samuel Graham (International Journal of Refrigeration, 2023)

Plate tectonic control of strontium concentration in Phanerozoic and Neoproterozoic seawater: Evidence from fluid inclusions in marine halite - Mebrahtu F. Weldeghebriel; Tim K. Lowenstein; Zhiguang Xia; Weiqiang Li (Geochimica et Cosmochimica Acta, 2023)

Extremely rapid, Lagrangian modeling of 2D flooding: A rivulet-based approach - W. Brent Daniel; Corinne Roth; Xue Li; Cindy Rakowski; Tim McPherson; David Judi (Environmental Modelling & Software, 2023)

The changing sulphur content of a northern Chinese dust storm: Initiation, attenuation and culmination - Xiaolei Feng; Longyi Shao; Tim Jones; Yaowei Li; Mengyuan Zhang; Shuoyi Ge; Yaxin Cao; Kelly BéruBé; Daizhou Zhang (Atmospheric Environment, 2023)

The race for space: Modelling the landward migration of coastal wetlands under sea level rise at regional scale - Li Wen; Tim M. Glasby; Michael G. Hughes (Science of The Total Environment, 2023)

Comparison of southward shift mechanisms of equatorial westerly anomalies between EP and CP El Niño - Yuhan Gong; Tim Li (Climate Dynamics, 2023)

Interannual and seasonal relationships between photosynthesis and summer soil moisture in the Ili River basin, Xinjiang, 2000–2018 - Tao Yu; Guli Jiapaer; Gang Long; Xu Li; Jingyu Jing; Ying Liu; Philippe De Maeyer; Tim Van de Voorde (Science of The Total Environment, 2023)

A new model for the segmentation, propagation and linkage of the Tan-Lu fault zone, East Asia - Chengming Li; Changhou Zhang; Tim D. Cope (Journal of Asian Earth Sciences, 2023)

Role of low-frequency wind variability in inducing WWBs during the onset of super El Niños - Yi-Kai Wu; Chi-Cherng Hong; Tim Li; An-Yi Huang (Climate Dynamics, 2023)

An Objective Method for Defining Meiyu Onset in Lower Reaches of the Yangtze River Basin - Wei Wang; Tim Li; Fei Xin; Zhiwei Zhu (Journal of Meteorological Research, 2022)

Fractal characterization of pore structure and its influence on CH4 adsorption and seepage capacity of low-rank coals - Guangyuan Mu; Haihai Hou; Jiaqiang Zhang; Yue Tang; Ya-nan Li; Bin Sun; Yong Li; Tim Jones; Yuan Yuan; Longyi Shao (Frontiers of Earth Science, 2022)

East Asian summer monsoon enhanced by COVID-19 - Chao He; Wen Zhou; Tim Li; Tianjun Zhou; Yuhao Wang (Climate Dynamics, 2022)

Characterizing spatiotemporal variations of polycyclic aromatic hydrocarbons in Taihu Lake, China - Aili Li; Tim aus der Beek; Jin Zhang; Cora Schmid; Christoph Schüth (Environmental Monitoring and Assessment, 2022)
In this study, we analyzed the concentration distributions of 20 polycyclic aromatic hydrocarbons (PAHs) in 41 water samples which were collected from the northern part of Taihu Lake during 4 field campaigns (201511, 201606, 201702 and 201709). The concentrations were determined with GC–MS, and their spatial and seasonal distribution characteristics were interpreted. The results show that 2-ring PAHs present considerably higher concentrations in warm seasons than cold seasons, but the concentrations of the other higher-ring PAHs are rather stable in warm and cold seasons. The distribution patterns of these PAHs might be mainly attributed to ambient temperature effects on the PAH solubility in the water body. Meanwhile, the spatial distributions of the PAH concentrations in cold seasons were rather various in the sampling area, while the distributions in the warm seasons were homogeneous. The different distributions could result from the water recharge from the Yangtze River during cold seasons, which diluted PAH concentrations in the northeastern part of the lake. Furthermore, via literature review on PAH concentrations in water body, PAHs are in a wide range of levels and their patterns are different among the studies, which should be more effected by local factors instead of general PAH properties. The results from this study also present special characteristics of PAHs in Taihu Lake, which exhibit more insight on PAHs existence in water bodies.

Prediction of the typhoon wind field in Hong Kong: integrating the effects of climate change using the Shared Socioeconomic Pathways - Jiayao Wang; Tim K. T. Tse; Sunwei Li; Jimmy C. H. Fung (Climate Dynamics, 2022)

An Empirical Model of Tropical Cyclone Intensity Forecast in the Western North Pacific - Chen Ma; Tim Li (Journal of Meteorological Research, 2022)

How Frequently Will the Persistent Heavy Rainfall over the Middle and Lower Yangtze River Basin in Summer 2020 Happen under Global Warming? - Zi-An Ge; Lin Chen; Tim Li; Lu Wang (Advances in Atmospheric Sciences, 2022)

Simulations of a Persistent Heat Wave Event in Missouri in Summer 2012 Using a High-Resolution WRF Model - Lili Zhu; Fengpeng Sun; Tim Li (Journal of Meteorological Research, 2022)

Heavy Precipitation over the Jing-Jin-Ji Region in Early October: What Controls Its Interannual Variability? - Jing Feng; Tim Li; Ji Wang; Linna Zhang (Journal of Meteorological Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Impacts of multi‐timescale circulations on meridional heat transport - Qiao Liu; Tim Li; Weican Zhou (International Journal of Climatology, 2022)
Relative contributions to the zonal mean meridional heat transport by the climatological annual mean, climatological annual variation, synoptic, intra‐seasonal and lower‐frequency motions were examined based on the ERA‐Interim reanalysis data for the period of 1981–2015. The meridional heat transport analysed in this study only includes the component related to meridional wind and temperature. In the tropics, the climatological annual mean circulations dominate the long‐term mean meridional heat transport, while the interaction between the climatological annual mean temperature and the seasonal anomalous flow largely contributes to the seasonal variation of the meridional heat transport. In the middle latitudes, the climatological annual mean circulations and transient eddies (mostly synoptic and intra‐seasonal eddies) are of roughly equal importance in the poleward heat transport, leading to the maximum poleward heat transport around 50°N/S. The upper‐ and lower‐tropospheric heat transports by the climatological annual mean circulations appear opposite, with the magnitude of the lower‐tropospheric transport being greater. The preferred maximum zonal mean heat transport at 50°N by the climatological mean flow is attributed to the maximum zonal mean low‐level southerly in situ. The preferred peak latitude of the mid‐latitude poleward heat transport by synoptic eddies near 50°N arises from the combined effect of the strong synoptic‐scale meridional wind and temperature variabilities in situ and their in‐phase relationship. The heat transport by tropical cyclones (TCs) was estimated by applying a statistical relationship between TC intensity and the vertically integrated temperature averaged over the TC core region derived from high‐resolution Weather Research and Forecasting (WRF) model simulations. For northern hemisphere summer, TCs contribute about 35% of the total heat transport in the active TC regions, suggesting that TCs play a critical role in the regional meridional heat transport.

Mapping the Green-Lipped Mussel (Perna canaliculus) Microbiome: A Multi-Tissue Analysis of Bacterial and Fungal Diversity - Siming Li; Tim Young; Stephen Archer; Kevin Lee; Shaneel Sharma; Andrea C. Alfaro (Current Microbiology, 2022)
Poor health and mortality events of the commercially important and endemic New Zealand green-lipped mussel ( Perna canaliculus ) pose a threat to its industry. Despite the known importance of microbiomes to animal health and environmental resilience, the host-associated microbiome is unexplored in this species. We conducted the first baseline characterization of bacteria and fungi within key host tissues (gills, haemolymph, digestive gland, and stomach) using high-throughput amplicon sequencing of 16S rRNA gene and ITS1 region for bacteria and fungi, respectively. Tissue types displayed distinctive bacterial profiles, consistent among individuals, that were dominated by phyla which reflect (1) a fluid exchange between the circulatory system (gills and haemolymph) and surrounding aqueous environment and (2) a highly diverse digestive system (digestive gland and stomach) microbiota. Gammaproteobacteria and Campylobacterota were mostly identified in the gill tissue and haemolymph, and were also found in high abundance in seawater. Digestive gland and stomach tissues were dominated by common gut bacterial phyla, such as Firmicutes , Cyanobacteria , Proteobacteria , and Bacteroidota , which reflects the selectivity of the digestive system and food-based influences. Other major notable taxa included the family Spirochaetaceae , and genera Endozoicomonas , Psychrilyobacter , Moritella and Poseidonibacter , which were highly variable among tissue types and samples. More than 50% of fungal amplicon sequence variants (ASVs) were unclassified beyond the phylum level, which reflects the lack of studies with marine fungi. However, the majority of those identified were assigned to the phylum Ascomycota . The findings from this work provide the first insight into healthy tissue microbiomes of P. canaliculus and is of central importance to understanding the effect of environmental changes on farmed mussels at the microbial level.

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Influence of El Niño decaying pace on low latitude tropical cyclogenesis over the western North Pacific - Changhao Lu; Xuyang Ge; Melinda Peng; Tim Li (International Journal of Climatology, 2022)
The modulation of El Niño decaying pace on tropical cyclones (TCs) activities at low latitude (within 10°) over the western North Pacific (WNP) is investigated in this study. During rapidly decaying El Niño events, fewer TCs occur near the equator and the averaged genesis location is more westward. More TCs are found in the southeast of WNP during slowly decaying phase of El Niño events. The distinctive differences of TC genesis frequency and their respective meridional positions are related to the modulation of El Niño to large‐scale environmental flows. Both dynamical and thermodynamical conditions, such as low‐level vorticity, mid‐level relative humidity and vertical motion, are favourable for TC genesis in the southeast of WNP during slowly decaying El Niño events. The differences of sea surface temperature, vertical wind shear, and TC heat potential between the two El Niño events are similar to the spatial distribution of TC genesis at low latitude. Disturbances in southeastern WNP in slowly decaying El Niño events are more likely to develop into TCs due to the stronger zonal convergence and meridional shear of zonal wind. These findings may help to better understand the interaction between low‐latitude TCs and El Niño. The higher frequency of low‐latitude TC genesis and their more eastward TC genesis position in slowly decaying El Niño events may in turn slow down the transition speed of El Niño.

The genetics of vigour-related traits in chickpea (Cicer arietinum L.): insights from genomic data - Duong T. Nguyen; Julie E. Hayes; Judith Atieno; Yongle Li; Ute Baumann; Angela Pattison; Helen Bramley; Kristy Hobson; Manish Roorkiwal; Rajeev K. Varshney; Timothy D. Colmer; Tim Sutton (Theoretical and Applied Genetics, 2022)

Erratum to: Implications from Subseasonal Prediction Skills of the Prolonged Heavy Snow Event over Southern China in Early 2008 - Keyue Zhang; Juan Li; Zhiwei Zhu; Tim Li (Advances in Atmospheric Sciences, 2022)

Relationship between the interannual and intraseasonal temperature variability in Northeast China - Wenhui Li; Guirong Tan; Tim Li (International Journal of Climatology, 2022)
A significant negative correlation between the seasonal mean temperature anomaly and the intensity of the intraseasonal temperature oscillation in the northern winter over Northeast China is found during the time period 1959–2011. A stronger intraseasonal oscillation (ISO) is found during an extremely cold winter. The cold winter in Northeast China is a part of zonally oriented large‐scale pattern with a negative (positive) temperature anomaly in mid‐ (high) latitudes and is associated with a negative phase of the North Atlantic Oscillation (NAO). The intraseasonal temperature anomaly originates from high‐latitude Central Eurasia and propagates southeastward. The southeastward propagation is attributed to the upper tropospheric dispersion of Rossby wave energy as a result of coupling of the low‐level temperature and the upper‐level geopotential height. The cause of the negative correlation between the intraseasonal and interannual modes is investigated. A cold winter in Northeast China is associated with a weakened meridional temperature gradient and vertical wind shear north of 50°N. This weakens synoptic variability in situ through baroclinic instability. Because the ISO competes for an energy source with the synoptic motion, the ISO is enhanced north of 50°N. The southeastward propagation of the enhanced ISO mode increased intraseasonal temperature variability over Northeast China. As a result, a cold winter in Northeast China is accompanied by an enhanced ISO variability in situ. The enhanced local ISO could further feedback to the winter mean temperature anomaly through nonlinear advective processes. The diagnosis of the temperature budget indicates that the ISO may interact with motion on other scales to contribute to the winter mean temperature anomaly in situ.

Biallelic variants in YRDC cause a developmental disorder with progeroid features - Julia Schmidt; Jonas Goergens; Tatiana Pochechueva; Annika Kotter; Niko Schwenzer; Maren Sitte; Gesa Werner; Janine Altmüller; Holger Thiele; Peter Nürnberg; Jörg Isensee; Yun Li; et al. (Human Genetics, 2021)
The highly conserved YrdC domain-containing protein (YRDC) interacts with the well-described KEOPS complex, regulating specific tRNA modifications to ensure accurate protein synthesis. Previous studies have linked the KEOPS complex to a role in promoting telomere maintenance and controlling genome integrity. Here, we report on a newborn with a severe neonatal progeroid phenotype including generalized loss of subcutaneous fat, microcephaly, growth retardation, wrinkled skin, renal failure, and premature death at the age of 12 days. By trio whole-exome sequencing, we identified a novel homozygous missense mutation, c.662T > C, in YRDC affecting an evolutionary highly conserved amino acid (p.Ile221Thr). Functional characterization of patient-derived dermal fibroblasts revealed that this mutation impairs YRDC function and consequently results in reduced t 6 A modifications of tRNAs. Furthermore, we established and performed a novel and highly sensitive 3-D Q-FISH analysis based on single-telomere detection to investigate the impact of YRDC on telomere maintenance. This analysis revealed significant telomere shortening in YRDC-mutant cells. Moreover, single-cell RNA sequencing analysis of YRDC-mutant fibroblasts revealed significant transcriptome-wide changes in gene expression, specifically enriched for genes associated with processes involved in DNA repair. We next examined the DNA damage response of patient’s dermal fibroblasts and detected an increased susceptibility to genotoxic agents and a global DNA double-strand break repair defect. Thus, our data suggest that YRDC may affect the maintenance of genomic stability. Together, our findings indicate that biallelic variants in YRDC result in a developmental disorder with progeroid features and might be linked to increased genomic instability and telomere shortening.

An Improved Method for Defining Short-Term Climate Anomalies - Xuan Chen; Tim Li (Journal of Meteorological Research, 2021)

Subseasonal and Synoptic Variabilities of Precipitation over the Yangtze River Basin in the Summer of 2020 - Liudan Ding; Tim Li; Ying Sun (Advances in Atmospheric Sciences, 2021)

Cause of Extreme Heavy and Persistent Rainfall over Yangtze River in Summer 2020 - Xiao Pan; Tim Li; Ying Sun; Zhiwei Zhu (Advances in Atmospheric Sciences, 2021)
Record-breaking heavy and persistent precipitation occurred over the Yangtze River Valley (YRV) in June-July (JJ) 2020. An observational data analysis has indicated that the strong and persistent rainfall arose from the confluence of southerly wind anomalies to the south associated with an extremely strong anomalous anticyclone over the western North Pacific (WNPAC) and northeasterly anomalies to the north associated with a high-pressure anomaly over Northeast Asia. A further observational and modeling study has shown that the extremely strong WNPAC was caused by both La Niña-like SST anomaly (SSTA) forcing in the equatorial Pacific and warm SSTA forcing in the tropical Indian Ocean (IO). Different from conventional central Pacific (CP) El Niños that decay slowly, a CP El Niño in early 2020 decayed quickly and became a La Niña by early summer. This quick transition had a critical impact on the WNPAC. Meanwhile, an unusually large area of SST warming occurred in the tropical IO because a moderate interannual SSTA over the IO associated with the CP El Niño was superposed by an interdecadal/long-term trend component. Numerical sensitivity experiments have demonstrated that both the heating anomaly in the IO and the heating anomaly in the tropical Pacific contributed to the formation and maintenance of the WNPAC. The persistent high-pressure anomaly in Northeast Asia was part of a stationary Rossby wave train in the midlatitudes, driven by combined heating anomalies over India, the tropical eastern Pacific, and the tropical Atlantic.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

Implications from Subseasonal Prediction Skills of the Prolonged Heavy Snow Event over Southern China in Early 2008 - Keyue Zhang; Juan Li; Zhiwei Zhu; Tim Li (Advances in Atmospheric Sciences, 2021)

Intraseasonal Variability of Summertime Surface Air Temperature over Mid-High-Latitude Eurasia and Its Prediction Skill in S2S Models - Jing Cui; Shuangyan Yang; Tim Li (Journal of Meteorological Research, 2021)

Decreasing Trend of Western North Pacific Tropical Cyclone Inner-Core Size over the Past Decades - Hanrui Shou; Tim Li; Yuan Sun; Lu Wang; Jia Liu (Journal of Meteorological Research, 2021)

How well do the S2S models predict intraseasonal wintertime surface air temperature over mid-high-latitude Eurasia? - Jing Cui; Shuangyan Yang; Tim Li (Climate Dynamics, 2021)

Cause of an extreme warm and rainy winter in Shanghai in 2019 - Xiao Pan; Wei Wang; Tim Li; Fei Xin; Jinhua Yu (International Journal of Climatology, 2021)
An extreme warm winter (ranked first during the past 30‐years) occurred in Shanghai in 2019, accompanied with an extreme rainy winter (ranked thirdly in the same period). An observational diagnosis shows that the extreme warm and rainy winter arose from southerly anomalies associated with an anticyclone east of Shanghai. The cause of the anticyclone was attributed to V‐shaped upper‐tropospheric Rossby wave activity fluxes, originated from the North Atlantic and tropical Indian Ocean. Numerical model experiments indicate that the anomalous heat source in the tropical Indian Ocean played a dominant role (~65%) in causing the local anomalous circulation, while the heating in North Atlantic also played a role (~35%). A further analysis of the past 30 year data revealed that an extreme warm winter in the past did not coincide with an extreme wet winter. While the warm winter composite shows a large‐scale anticyclone anomaly over Central and East Asia, the rainy winter composite exhibits a circulation dipole pattern with an anomalous cyclone (anticyclone) west (east) of Shanghai. Numerical experiments confirm that the former was forced by the combined effect of precipitation anomalies over the North Atlantic and tropical Indian Ocean (IO) and Maritime Continent (MC) through Rossby wave energy dispersion, whereas the latter was caused by a dipole heating pattern over the tropical IO/MC sector.

ENSO evolution asymmetry: EP versus CP El Niño - Mingcheng Chen; Tim Li (Climate Dynamics, 2021)

A mechanism for formation of the western North Pacific monsoon trough: nonlinear upscale cascade - Chi Qin; Tim Li; Jia Liu; Mingyu Bi (Climate Dynamics, 2021)

Impacts of Steering Flows with Different Timescales on the Track of Typhoon Sanba (2012) - Qiao Liu; Melinda Peng; Weican Zhou; Tim Li (Journal of Meteorological Research, 2021)

Evaluating the Impact of Calcification on Plaque Vulnerability from the Aspect of Mechanical Interaction Between Blood Flow and Artery Based on MRI - Jessica Benitez; Davide Fontanarosa; Jiaqiu Wang; Phani Kumari Paritala; Tim McGahan; Thomas Lloyd; Zhiyong Li (Annals of Biomedical Engineering, 2021)

Effects of perturbation type on tropical cyclone size over tropical North Western Pacific and Atlantic - Chen Ma; Tim Li (Climate Dynamics, 2021)

Mid‐latitude leading double‐dip La Niña - Jae‐Heung Park; Soon‐Il An; Jong‐Seong Kug; Young‐Min Yang; Tim Li; Hyun‐Su Jo (International Journal of Climatology, 2021)
Understanding the evolution asymmetry between El Niño and La Niña events is challenging. Unlike El Niño, most La Niña events are characterised by a double‐dip cooling (a.k.a. multi‐year La Niña). Herein, we examined how single‐ and multi‐year La Niña events differ by analysing observational and climate‐model data sets. Single‐year La Niña events tend to develop narrowly within the tropics from a central Pacific‐type El Niño (Niño‐4 > Niño‐3), whereas multi‐year La Niña events tend to originate from an eastern Pacific‐type El Niño (Niño‐3 > Niño‐4) and are well‐connected to mid‐latitudes through the Pacific meridional mode , which leads to a meridionally wider response of the off‐equatorial low‐level atmospheric anti‐cyclonic circulation. As the anti‐cyclonic circulation controls the amount of equatorial upper‐ocean heat recharge through Sverdrup transport, for single‐year La Niña, efficient ocean recharging due to a narrower anti‐cyclonic circulation causes a fast transition to an El Niño or a fast termination of a La Niña. In contrast, for multi‐year La Niña, a weaker recharging causes surface cooling to persist, leading to another La Niña in the following year.

Impact of ENSO on MJO Pattern Evolution over the Maritime Continent - Jia Liu; Yuqin Da; Tim Li; Feng Hu (Journal of Meteorological Research, 2020)

Forecasts of ENSO evolution using spatial–temporal projection model - Xiao Pan; Zhiwei Zhu; Tim Li (International Journal of Climatology, 2020)
El Niño–Southern Oscillation (ENSO) prediction is one of the most debated and challenging tasks, whilst its real‐time operational prediction skill still has room for improvement. In this study, spatial–temporal projection model is applied to predict Niño3.4 index at lead time of one to six months. By regressing variable fields onto Niño3.4 index month by month, physical‐based predictability sources, that is, the mixed‐layer oceanic temperature, sea surface temperature, thermocline depth, and accumulated westerly‐wind‐events index over the specific regions are detected as the predictors. Based on the temporal evolution of coupled modes of predictors and Niño3.4 index, the Niño3.4 index from JAS (July, August, and September) to DJF (December, January, and February) can be predicted once a year. The model could nicely reproduce the evolution of Niño3.4 index from JAS to DJF. It also achieved high prediction skills for the year‐to‐year DJF Niño3.4 index, with a root‐mean‐square error of 0.46 in the training period (1950–2000) and 0.52 in the independent‐forecast period (2001–2016). Further investigation shows that the forecast is more reliable when the forecasted ENSO amplitude is much larger.

Enhanced winter and summer trend difference of Madden–Julian Oscillation intensity since 1871 - Ziyue Wang; Tim Li; Jianyun Gao; Melinda Peng (International Journal of Climatology, 2020)
Long‐term winter and summer Madden–Julian Oscillation (MJO) trends in the past 138 years (1871–2008) were examined using National Oceanic and Atmospheric Administration (NOAA) 20th Century Reanalysis V2c dataset. It is found that MJO shows a distinctive different trend between boreal winter and summer. While the MJO intensity in both boreal winter and summer has a rising trend, the winter trend is much greater than the summer trend. As a result, the winter–summer difference shows a significant increasing trend. The distinctive winter and summer trends are attributed to the difference of atmospheric background circulation (such as vertical velocity) and static stability responses to the global warming between boreal winter and summer over equatorial eastern Indian Ocean. In boreal winter, both the surface moistening and strengthened inter‐tropical convergence zone convection contribute to an increase of MJO activity. This is in contrast to boreal summer when a greater static stability and anomalous subsidence tend to offset the moistening effect, leading to a relatively weaker increase of the MJO activity.

Interdecadal modulation of ENSO amplitude by the Atlantic multi-decadal oscillation (AMO) - Yuhan Gong; Tim Li; Lin Chen (Climate Dynamics, 2020)

El Niño phase-dependent high-frequency variability in Western Equatorial Pacific - Ming Sun; Tim Li; Lin Chen (Climate Dynamics, 2020)

Increasing Trend of Summertime Synoptic Wave Train Activity over the Western North Pacific since 1950 - Xinyi Zhou; Tim Li (Journal of Meteorological Research, 2020)

Impact of Background Dynamic and Thermodynamic States on Distinctive Annual Cycle of Near-Equatorial Tropical Cyclogenesis over the Western North Pacific - Liyuan Deng; Tim Li (Journal of Meteorological Research, 2020)

Female spider aggression is associated with genetic underpinnings of the nervous system and immune response to pathogens - Chia‐chen Chang; Heidi Connahs; Estella Cai Yu Tan; Y. Norma‐Rashid; Mrinalini; Daiqin Li; Fook Tim Chew (Molecular Ecology, 2020)
Identifying the genetic architecture underlying phenotypic variation in natural populations and assessing the consequences of polymorphisms for individual fitness are fundamental goals in evolutionary and molecular ecology. Consistent between‐individual differences in behaviour have been documented for a variety of taxa. Dissecting the genetic basis of such behavioural differences is however a challenging endeavour. The molecular underpinnings of natural variation in aggression remain elusive. Here, we used comparative gene expression (transcriptome analysis and RT–PCR), genetic association analysis and pharmacological experiments to gain insight into the genetic basis of aggression in wild‐caught jumping spiders ( Portia labiata ). We show that spider aggression is associated with a putative viral infection response gene, BTB/POZ domain‐containing protein 17 (BTBDH), in addition to a putative serotonin receptor 1A (5‐HT1A) gene. Spider aggression varies with virus loads, and BTBDH is upregulated in docile spiders and exhibits a genetic variant associated with aggression. We also identify a putative serotonin receptor 5‐HT1A gene upregulated in docile P. labiata . Individuals that have been treated with serotonin become less aggressive, but individuals treated with a nonselective serotonin receptor antagonist (methiothepin) also reduce aggression. Further, we identify the genetic variants in the 5‐HT1A gene that are associated with individual variation in aggression. We therefore conclude that co‐evolution of the immune and nervous systems may have shaped the between‐individual variation in aggression in natural populations of jumping spiders.

Diverse Asgard archaea including the novel phylum Gerdarchaeota participate in organic matter degradation - Mingwei Cai; Yang Liu; Xiuran Yin; Zhichao Zhou; Michael W. Friedrich; Tim Richter-Heitmann; Rolf Nimzyk; Ajinkya Kulkarni; Xiaowen Wang; Wenjin Li; Jie Pan; Yuchun Yang; et al. (Science China Life Sciences, 2020)

Diagnosing the column-integrated moist static energy budget associated with the northward-propagating boreal summer intraseasonal oscillation - Tianyi Wang; Tim Li (Climate Dynamics, 2020)

Effects of high-frequency surface wind on the intraseasonal SST associated with the Madden-Julian oscillation - Yingxia Gao; Pang-Chi Hsu; Lin Chen; Lu Wang; Tim Li (Climate Dynamics, 2020)

Effects of western Pacific intraseasonal convection on surface air temperature anomalies over North America - Ying Yang; Zhiwei Zhu; Tim Li; Mengying Yao (International Journal of Climatology, 2020)
Using the daily outgoing longwave radiation and 850‐hPa zonal wind over (10°S–30°N, 105°–150°E) during the extended boreal summer (May to October), the lifecycle of the western Pacific intraseasonal oscillation (WPISO) is divided into eight phases based on the first two principle components of multivariate empirical orthogonal function decomposition. Because of the pronounced northward propagation feature, the meridional location of the convection anomaly centre in each WPISO phase is quite different, leading to distinct surface air temperature (SAT) anomaly responses over the Northern Hemisphere, in which North America shows the most significant SAT anomalies, and the SAT anomalies vary significantly with WPISO phase. Under different WPISO phases, convection can induce different mid‐to‐high latitude Rossby wave trains emanating from East Asia to North America, resulting in different SAT anomaly patterns over North America. Four numerical experiments are conducted and demonstrate that the convection at different meridional locations in each WPISO phase could shape the pattern of the Rossby wave train and in turn lead to different SAT anomalies over North America. The results in this study are expected to provide predictability sources for the sub‐seasonal‐to‐seasonal (S2S) prediction of North American SAT anomalies.

The 10–30‐day oscillation of winter rainfall in southern China and its relationship with circulation patterns in different latitudes - Suxiang Yao; Qiaoyu Tong; Tim Li; Kejian Gong (International Journal of Climatology, 2020)
Intraseasonal oscillation (ISO) of winter rainfall in southern China and its relationship with the circulation patterns in different latitudes are investigated using ERA‐Interim reanalysis data and observations. The results show that the rainfall in southern China has obvious ISO characteristics, with a dominant period of 10–30 days. The convergence of the whole layer integral water vapour flux can satisfactorily represent the rainfall rate, and the intraseasonal (10–30‐day filtered) rainfall is converted into a function of different time scale wind and water vapour. At the intraseasonal time scale, rainfall (10–30‐day filtered) is determined by both the 10–30‐day wind and the background (greater than 30 days) moisture. Nine days before the peak day of the intraseasonal rainfall in southern China, there is an abnormal low‐pressure system (10–30‐day filtered) in the polar region (east to Novaya Zemlya), and the low‐pressure system gradually strengthens because of the intraseasonal relative vorticity advection at high levels. The intraseasonal relative vorticity advection guides the intraseasonal geopotential anomaly to move from the high latitude to the low latitude, and the low‐pressure system at the surface also moves southward. There is no intraseasonal precipitation until the low‐pressure system at the surface moves to the region near southern China, because there is little water vapour in northern China and ample water vapour in the south. After the occurrence of precipitation, the vorticity advection from the high latitude no longer affects the strength of the low‐pressure system, but the intraseasonal diabatic heating accompanied by precipitation causes a second drop in pressure from −3 days to −1 day and makes the low‐pressure system strongest here. In addition, the geopotential anomaly (10–30‐day filtered) in low latitudes moves eastward along the southern foothills of the Tibetan plateau, which can guide the low‐pressure system to move southward until it reaches southern China.

Seasonal and Sub-Seasonal Circulation Anomalies Associated with Persistent Rainy Days in 2018/2019 Winter in Shanghai, China - Wei Wang; Fei Xin; Xiao Pan; Ying Zhang; Tim Li (Journal of Meteorological Research, 2020)

Seasonal Prediction of Boreal Winter Rainfall over the Western Maritime Continent during ENSO - Chih-Pei Chang; Tim Li; Song Yang (Journal of Meteorological Research, 2020)

Characterization of tropical cyclone rapid intensification under two types of El Niño events in the Western North Pacific - Donglei Shi; Xuyang Ge; Melinda Peng; Tim Li (International Journal of Climatology, 2020)
This study investigates the impacts of two different El Niño scenarios, the east Pacific warming El Niño (EPW) and the central Pacific warming El Niño (CPW), on the tropical cyclone (TC) rapid intensification (RI) in the western North Pacific (WNP). The ratio of TCs with at least one RI occurrence (RITC) to all TC numbers (RITC ratio) shows different monthly variations between the two El Niño groups. Higher RITC ratio is found during July–October (November–December) for the EPW (CPW) years. Further analyses indicate that the difference in the RITC ratio is attributed to differences in TC genesis locations, TC tracks and large‐scale environmental conditions. During July–October (TC peak season), TCs formed more in the southeastern region with EPW than with CPW. TCs in the southeastern WNP tend to move westward (northward) in the presence of weak (significant southerly) steering flow anomalies in EPW (CPW), allowing a longer (shorter) duration over the warm tropical ocean. Meanwhile, a smaller environmental vertical wind shear is also observed in the main RI region with EPW. These two mechanisms contribute to a higher peak‐season RITC ratio in the EPW years. During November–December (late season) of the EPW years, the southern WNP is dominated by anomalous anticyclonic flow that suppresses TC genesis and intensification, which leads to notably less TC frequency and RITC ratio. The anomalous equatorial heating source near the dateline induces cyclonic flow in the southeastern WNP through Gill‐type response during the late season in CPW years. The resulting larger low‐level relative vorticity, stronger upward motion, higher mid‐level relative humidity and weaker vertical wind shear all favour TCs genesis over the southeastern WNP and their subsequent intensification in the main RI region . In addition, a greater TC heat potential is evident during the late season in CPW. Hence, the more favourable atmospheric and oceanic conditions result in a greater late‐season RITC ratio in CPW than in EPW.

Effect of vertical moist static energy advection on MJO eastward propagation: sensitivity to analysis domain - Lu Wang; Tim Li (Climate Dynamics, 2020)

Change of El Niño and La Niña amplitude asymmetry around 1980 - Xiao Pan; Tim Li; Mingcheng Chen (Climate Dynamics, 2020)

Madden-Julian Oscillation: Its Discovery, Dynamics, and Impact on East Asia - Tim Li; Jian Ling; Pang-Chi Hsu (Journal of Meteorological Research, 2020)

Origins of Quasi-Biweekly and Intraseasonal Oscillations over the South China Sea and Bay of Bengal and Scale Selection of Unstable Equatorial and Off-Equatorial Modes - Ying Zhang; Tim Li; Jianyun Gao; Wei Wang (Journal of Meteorological Research, 2020)

Tropical Cyclone Size Change under Ocean Warming and Associated Responses of Tropical Cyclone Destructiveness: Idealized Experiments - Zanmin Xu; Yuan Sun; Tim Li; Zhong Zhong; Jia Liu; Chen Ma (Journal of Meteorological Research, 2020)

Can reanalysis products with only surface variables assimilated capture Madden–Julian oscillation characteristics? - Jingxuan Cui; Lu Wang; Tim Li; Bo Wu (International Journal of Climatology, 2020)
The Madden–Julian Oscillation (MJO), as a dominant mode of tropical intraseasonal oscillation, plays an important role in the variability of global weather and climate. However, current state‐of‐the‐art atmospheric circulation models have difficulty in reproducing observed MJO characteristics when forced by observed daily sea surface temperature alone. An important practical question is how much data a model needs in assimilation to reproduce real MJO events? By analysing ERA‐20C and NOAA‐20CR reanalysis data, the authors tried to figure out whether a model could reproduce observed MJO events by assimilating the observed surface signal alone. The phase propagation and vertical structure associated with MJO were compared between the reanalysis data and observations during 1979–2010. A total skill score considering both temporal correlation and spatial standard deviation were defined. The result showed that both ERA‐20C and NOAA‐20CR could reproduce the observed MJO characteristics very well, with the former superior to the latter, regardless of MJO intensity. Thus, a minimum requirement for an operational atmospheric model for MJO prediction is the assimilation of the observed surface signals.

Two-way interactions between MJO and high-frequency waves over the Maritime Continent in MJOTF/GASS models - Yan Zhu; Tim Li (Climate Dynamics, 2020)

Response of the anomalous western North Pacific anticyclone during El Niño mature winter to global warming - Yuhao Wang; Chao He; Tim Li (Climate Dynamics, 2020)

Forecasts of MJO Events during DYNAMO with a Coupled Atmosphere-Ocean Model: Sensitivity to Cumulus Parameterization Scheme - Mei-Yu Chang; Tim Li; Pay-Liam Lin; Ting-Huai Chang (Journal of Meteorological Research, 2019)

Factors controlling northward and north-eastward moving tropical cyclones near the coast of East Asia - Qiao Liu; Weican Zhou; Melinda Peng; Tim Li (Frontiers of Earth Science, 2019)

Precipitation diurnal cycle over the Maritime Continent modulated by the MJO - Jiahao Lu; Tim Li; Lu Wang (Climate Dynamics, 2019)

A coupled moisture-dynamics model of the Madden–Julian oscillation: convection interaction with first and second baroclinic modes and planetary boundary layer - Tim Li; Feng Hu (Climate Dynamics, 2019)

Changes of MJO propagation characteristics under global warming - Jingxuan Cui; Tim Li (Climate Dynamics, 2019)

Relative roles of El Niño-induced extratropical and tropical forcing in generating Tropical North Atlantic (TNA) SST anomaly - Leishan Jiang; Tim Li (Climate Dynamics, 2019)

Mechanism for asymmetric atmospheric responses in the western North Pacific to El Niño and La Niña - Xiaohui Wang; Tim Li; Mingcheng Chen (Climate Dynamics, 2019)

Asymmetry of Atmospheric Responses to Two-Type El Niño and La Niña over Northwest Pacific - Mingcheng Chen; Tim Li; Xiaohui Wang (Journal of Meteorological Research, 2019)

Snowmelt and early to mid‐growing season water availability augment tree growth during rapid warming in southern Asian boreal forests - Xianliang Zhang; Rubén D. Manzanedo; Loïc D'Orangeville; Tim T. Rademacher; Junxia Li; Xueping Bai; Meiting Hou; Zhenju Chen; Fenghua Zou; Fangbo Song; Neil Pederson (Global Change Biology, 2019)
Boreal forests are facing profound changes in their growth environment, including warming‐induced water deficits, extended growing seasons, accelerated snowmelt, and permafrost thaw. The influence of warming on trees varies regionally, but in most boreal forests studied to date, tree growth has been found to be negatively affected by increasing temperatures. Here, we used a network of Pinus sylvestris tree‐ring collections spanning a wide climate gradient the southern end of the boreal forest in Asia to assess their response to climate change for the period 1958–2014. Contrary to findings in other boreal regions, we found that previously negative effects of temperature on tree growth turned positive in the northern portion of the study network after the onset of rapid warming. Trees in the drier portion did not show this reversal in their climatic response during the period of rapid warming. Abundant water availability during the growing season, particularly in the early to mid‐growing season (May–July), is key to the reversal of tree sensitivity to climate. Advancement in the onset of growth appears to allow trees to take advantage of snowmelt water, such that tree growth increases with increasing temperatures during the rapidly warming period. The region's monsoonal climate delivers limited precipitation during the early growing season, and thus snowmelt likely covers the water deficit so trees are less stressed from the onset of earlier growth. Our results indicate that the growth response of P. sylvestris to increasing temperatures strongly related to increased early season water availability. Hence, boreal forests with sufficient water available during crucial parts of the growing season might be more able to withstand or even increase growth during periods of rising temperatures. We suspect that other regions of the boreal forest may be affected by similar dynamics.

Interannual relationship between intensity of rainfall intraseasonal oscillation and summer-mean rainfall over Yangtze River Basin in eastern China - Yanjun Qi; Tim Li; Renhe Zhang; Yang Chen (Climate Dynamics, 2019)

Role of the western hemisphere warm pool in climate variability over the western North Pacific - Jae-Heung Park; Jong-Seong Kug; Soon-Il An; Tim Li (Climate Dynamics, 2019)

Contrast of Evolution Characteristics of Boreal Summer and Winter Intraseasonal Oscillations over Tropical Indian Ocean - Qingchi Zhang; Tim Li; Jia Liu (Journal of Meteorological Research, 2019)

A Further Study on the Simulation of Cloud-Radiative Feedbacks in the ENSO Cycle in the Tropical Pacific with a Focus on the Asymmetry - Lin Chen; De-Zheng Sun; Lu Wang; Tim Li (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Effect of recent Atlantic warming in strengthening Atlantic–Pacific teleconnection on interannual timescale via enhanced connection with the pacific meridional mode - Jae-Heung Park; Tim Li; Sang-Wook Yeh; Heyrim Kim (Climate Dynamics, 2019)

Drivers of reduced ENSO variability in mid-Holocene in a coupled model - Lin Chen; Lu Wang; Tim Li; Jian Liu (Climate Dynamics, 2019)

Basin dependence of the MJO modulating tropical cyclone genesis - Chen Zhao; Tim Li (Climate Dynamics, 2019)

Interdecadal modulation of El Niño–tropical North Atlantic teleconnection by the Atlantic multi-decadal oscillation - Jae-Heung Park; Tim Li (Climate Dynamics, 2019)

Influence of ENSO on frequency of wintertime fog days in Eastern China - Huaying Yu; Tim Li; Peng Liu (Climate Dynamics, 2019)

Life table invasion models: spatial progression and species‐specific partitioning - Zihua Zhao; Cang Hui; Richard E. Plant; Min Su; Tim Carpenter; Nikos Papadopoulos; Zhihong Li; James R. Carey (Ecology, 2019)
Biological invasions are increasingly being considered important spatial processes that drive global changes, threatening biodiversity, regional economies, and ecosystem functions. A unifying conceptual model of the invasion dynamics could serve as a useful tool for comparison and classification of invasion processes involving different species across large geographic ranges. By dividing these geographic ranges that are subject to invasions into discrete spatial units, we here conceptualize the invasion process as the transition from pristine to invaded spatial units. We use California cities as the spatial units and a long‐term database of invasive tropical tephritids to characterize the invasion patterns. A new life‐table method based on insect demography, including the progression model of invasion stage transition and the species‐specific partitioning model of multispecies invasions, was developed to analyze the invasion patterns. The progression model allows us to estimate the probability and rate of transition for individual cities from pristine to infested stages and subsequently differentiate the first year of detection from detection recurrences. Importantly, we show that the interval of invasive tephritid recurrence in a city declines with increasing invasion stages of the city. The species‐specific partitioning model revealed profound differences in invasion outcome depending on which tephritid species was first detected (and then locally eradicated) in the early stage of invasion. Taken together, we discuss how these two life‐table invasion models can cast new light on existing invasion concepts; in particular, on formulating invasion dynamics as the state transition of cities and partitioning species‐specific roles during multispecies invasions. These models provide a new set of tools for predicting the spatiotemporal progression of invasion and providing early warnings of recurrent invasions for efficient management.

Mapping resistance to Phytophthora root rot identifies independent loci from cultivated (Cicer arietinum L.) and wild (Cicer echinospermum P.H. Davis) chickpea - Amritha Amalraj; Julian Taylor; Sean Bithell; Yongle Li; Kevin Moore; Kristy Hobson; Tim Sutton (Theoretical and Applied Genetics, 2019)

Modulation of the Madden–Julian oscillation on the energetics of wintertime synoptic-scale disturbances - Lu Wang; Tim Li; Lin Chen (Climate Dynamics, 2019)

Environmental conditions regulating the formation of super tropical cyclone during pre-monsoon transition period over Bay of Bengal - Zhi Li; Tim Li; Weidong Yu (Climate Dynamics, 2019)

Why SST trend in North Pacific is peculiarly negative against warming trend elsewhere since 1958 - Yu Huang; Tim Li; Bo Wu (Climate Dynamics, 2019)

Unexpected large-scale atmospheric response to urbanization in East China - Hongyun Ma; Tim Li; Zhihong Jiang; Peng Gu (Climate Dynamics, 2019)

Effects of background state on tropical cyclone size over the Western North Pacific and Northern Atlantic - Chen Ma; Melinda Peng; Tim Li; Yuan Sun; Jia Liu; Mingyu Bi (Climate Dynamics, 2019)

Validity of parameter optimization in improving MJO simulation and prediction using the sub-seasonal to seasonal forecast model of Beijing Climate Center - Xiangwen Liu; Weijing Li; Tongwen Wu; Tim Li; Weizong Gu; Zongkai Bo; Beng Yang; Li Zhang; Weihua Jie (Climate Dynamics, 2019)

Near-equatorial tropical cyclone formation in western North Pacific: peak season and controlling parameter - Yan Li; Tim Li; Caifang Fu; Pang-Chi Hsu (Climate Dynamics, 2019)

Does global warming amplify interannual climate variability? - Chao He; Tim Li (Climate Dynamics, 2019)

Effects of high-frequency activity on latent heat flux of MJO - Yingxia Gao; Pang-Chi Hsu; Tim Li (Climate Dynamics, 2019)

The Role of Latent Heat Flux in Tropical Cyclogenesis over the Western North Pacific: Comparison of Developing versus Non-Developing Disturbances - Si Gao; Shengbin Jia; Yanyu Wan; Tim Li; Shunan Zhai; Xinyong Shen (Journal of Marine Science and Engineering, 2019)
The possible role of air–sea latent heat flux (LHF) in tropical cyclone (TC) genesis over the western North Pacific (WNP) is investigated using state-of-the-art satellite and analysis datasets. The authors conducted composite analyses of several meteorological variables after identifying developing and non-developing tropical disturbances from June to October of the period 2000 to 2009. Compared to the non-developing disturbances, increased LHF underlying the developing disturbances enhances boundary–layer specific humidity. The secondary circulation then transports more boundary–layer moisture inward and upward and, thus, induces a stronger moist core in the middle troposphere. Accordingly, the air in the core region ascends following a warmer moist adiabat than that in the environment and results in a stronger upper-level warm core, which is associated with a stronger near-surface tangential wind based on the thermal wind balance. This enlarges the magnitude and negative radial gradient of LHF and, thereby, further increases boundary–layer specific humidity. A tropical depression forms when the near-surface tangential wind increases to a certain extent as a result of the continuing positive feedback between near-surface wind and LHF. The results suggest an important role of wind-driven LHF in TC genesis over the WNP.

Decadal change in the relationship between East Asian spring circulation and ENSO: Is it modulated by Pacific Decadal Oscillation? - Yuhao Wang; Chao He; Tim Li (International Journal of Climatology, 2019)
Using the NOAA‐CIRES 20th century Reanalysis and the ERA‐20C reanalysis, the decadal changes in the relationship between East Asian spring circulation (EASC) and ENSO over the past century are investigated. These two datasets consistently show that a decadal change occurred around 1972 for the late 20th century, which coincides with the shift of Pacific Decadal Oscillation (PDO) from the negative to the positive phase. While the interannual variability of EASC is closely related to El Niño‐Southern Oscillation (ENSO) during 1973–2000, it is weakly related to ENSO but seems to be dominated by midlatitude atmospheric variability during 1952–1972. However, the relationship between EASC and ENSO is inconsistent between the two reanalysis datasets in the first half of the 20th century, raising a question whether PDO does have a modulation on the ENSO–EASC relationship or it just occurred by chance in 1970s. The pre‐industrial control (PIC) experiment of the coupled models from CMIP5 are analysed to address this question. In the long‐term simulation of the coupled models under fixed external forcing, the relationship between ENSO and EASC does show substantial decadal oscillation, just as in the observation, but the strength of the ENSO–EASC relationship is not substantially in phase with PDO. Forced by observed sea surface temperature from 1950 to 2010, an atmospheric general circulation model corroborates that the EASC–ENSO relation is almost steady after removing the atmospheric internal variability regardless of the phase of PDO, but it is subject to strong decadal oscillation in the multiple ensemble members with the stochastic modulation of atmospheric internal dynamics. These modelling evidences support the null hypothesis that the relationship between EASC and ENSO is not modulated by PDO.

East Asian climate under global warming: understanding and projection - Jianping Li; Huang-Hsiung Hsu; Wei-Chyung Wang; Kyung-Ja Ha; Tim Li; Akio Kitoh (Climate Dynamics, 2018)

Why 1986 El Niño and 2005 La Niña evolved different from a typical El Niño and La Niña - Mingcheng Chen; Tim Li (Climate Dynamics, 2018)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Relationship between the North Pacific Gyre Oscillation and the onset of stratospheric final warming in the northern Hemisphere - Jinggao Hu; Tim Li; Haiming Xu (Climate Dynamics, 2018)

Physical processes controlling earlier and later onset of a typhoon season in the western North Pacific - Heng Zuo; Tim Li; Jia Liu; Melinda Peng (Climate Dynamics, 2018)

Effects of intraseasonal oscillation on South China Sea summer monsoon onset - Hui Wang; Fei Liu; Bin Wang; Tim Li (Climate Dynamics, 2018)

Why rainfall response to El Niño over Maritime Continent is weaker and non-uniform in boreal winter than in boreal summer - Leishan Jiang; Tim Li (Climate Dynamics, 2018)

Influence of the Boreal Summer Intraseasonal Oscillation on Extreme Temperature Events in the Northern Hemisphere - Yifei Diao; Tim Li; Pang-Chi Hsu (Journal of Meteorological Research, 2018)

Modulation of the MJO intensity over the equatorial western Pacific by two types of El Niño - Lu Wang; Tim Li; Lin Chen; Swadhin K. Behera; Tomoe Nasuno (Climate Dynamics, 2018)

Cause of interdecadal change of tropical cyclone controlling parameter in the western North Pacific - Feng Hu; Tim Li; Jia Liu; Melinda Peng (Climate Dynamics, 2018)

Impact of 10–60-Day Low-Frequency Steering Flows on Straight Northward-Moving Typhoon Tracks over the Western North Pacific - Qiao Liu; Tim Li; Weican Zhou (Journal of Meteorological Research, 2018)

Divergent El Niño responses to volcanic eruptions at different latitudes over the past millennium - Fei Liu; Jinbao Li; Bin Wang; Jian Liu; Tim Li; Gang Huang; Zhiyuan Wang (Climate Dynamics, 2018)

Amplified contiguous United States summer rainfall variability induced by East Asian monsoon interdecadal change - Zhiwei Zhu; Tim Li (Climate Dynamics, 2018)

Extended-range forecasting of Chinese summer surface air temperature and heat waves - Zhiwei Zhu; Tim Li (Climate Dynamics, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

On the asymmetric distribution of shear-relative typhoon rainfall - Si Gao; Shunan Zhai; Tim Li; Zhifan Chen (Meteorology and Atmospheric Physics, 2018)

Dependence of Tropical Cyclone Intensification on the Latitude under Vertical Shear - Mingyu Bi; Xuyang Ge; Tim Li (Journal of Meteorological Research, 2018)

Protoplasts in the analysis of early plant-pathogen interactions: current applications and perspectives - Tim Xing; Xiu-Qing Li; Andre Laroche; Lining Tian; Kipkios Tubei; Xiaojing Wang (European Journal of Plant Pathology, 2017)

A possible explanation for the divergent projection of ENSO amplitude change under global warming - Lin Chen; Tim Li; Yongqiang Yu; Swadhin K. Behera (Climate Dynamics, 2017)

Theories on formation of an anomalous anticyclone in western North Pacific during El Niño: A review - Tim Li; Bin Wang; Bo Wu; Tianjun Zhou; Chih-Pei Chang; Renhe Zhang (Journal of Meteorological Research, 2017)

Extended-range forecast for the temporal distribution of clustering tropical cyclogenesis over the western North Pacific - Zhiwei Zhu; Tim Li; Long Bai; Jianyun Gao (Theoretical and Applied Climatology, 2017)

Development and Application of Urban High Temporal-Spatial Resolution Vehicle Emission Inventory Model and Decision Support System - Yi Zhang; Lin Wu; Chao Zou; Boyu Jing; Xiaoyu Li; Tim Barlow; Turpin Kevin; Michel André; Yao Liu; Peipei Ren; Gongdong Wang; Hongjun Mao (Environmental Modeling & Assessment, 2017)

Causes of intraseasonal diabatic heating variability over and near the Tibetan Plateau in boreal summer - Shuangyan Yang; Tim Li (Climate Dynamics, 2017)

The role of intraseasonal variability at mid‐high latitudes in regulating Pacific blockings during boreal winter - Shuangyan Yang; Tim Li (International Journal of Climatology, 2017)
By using daily National Centers for Environmental Prediction‐Department of Energy reanalysis data from 1979 to 2015, we investigated the connection between Pacific blockings and mid‐high latitude atmospheric intraseasonal oscillation ( ISO ) at 500 hPa in boreal winter. The ISO perturbation over a key area of 150 ° E–155 ° W, 60 ° –75 ° N is most co‐variated with Pacific blockings. The averaged geopotential height over this key area exhibits a statistically significant 10–35‐day periodicity. The ISO perturbation associated with the Pacific blocking activity shows pronounced westward propagation. The perturbation initiates at about 120 ° W, triggered by intraseasonal wave energy accumulation. A geopotential tendency diagnosis reveals that the time change rate of the geopotential height over the key area is primarily attributed to the advection of planetary vorticity by the ISO meridional flow. A mechanism is put forward in which the westward‐propagating ISO perturbations induce a blocking over the Pacific sector. When a strong northward ISO flow arrives in the key area, it acts against the gradient of planetary vorticity, leading to a negative vorticity advection. This negative advection tends to strengthen local anticyclonic vorticity and geopotential height anomalies. Thus, the westward‐propagating ISO meridional flow plays an active role in inducing the low‐frequency blocking activity over the Pacific sector.

Heterozygous HNRNPU variants cause early onset epilepsy and severe intellectual disability - Nuria C. Bramswig; Hermann-Josef Lüdecke; Fadi F. Hamdan; Janine Altmüller; Filippo Beleggia; Nursel H. Elcioglu; Catharine Freyer; Erica H. Gerkes; Yasemin Kendir Demirkol; Kelly G. Knupp; Alma Kuechler; Yun Li; et al. (Human Genetics, 2017)

Lessened response of boreal winter stratospheric polar vortex to El Niño in recent decades - Jinggao Hu; Tim Li; Haiming Xu; Shuangyan Yang (Climate Dynamics, 2017)

Physical processes responsible for the interannual variability of sea ice concentration in Arctic in boreal autumn since 1979 - Lei Zhang; Tim Li (Journal of Meteorological Research, 2017)

A nanomechanical study of the effects of colistin on the Klebsiella pneumoniae AJ218 capsule - Anna Mularski; Jonathan Wilksch; Eric Hanssen; Jian Li; Takehiro Tomita; Sacha James Pidot; Tim Stinear; Frances Separovic; Dick Strugnell (European Biophysics Journal, 2017)

MJO prediction using the sub-seasonal to seasonal forecast model of Beijing Climate Center - Xiangwen Liu; Tongwen Wu; Song Yang; Tim Li; Weihua Jie; Li Zhang; Zaizhi Wang; Xiaoyun Liang; Qiaoping Li; Yanjie Cheng; Hongli Ren; Yongjie Fang; et al. (Climate Dynamics, 2017)

Decadal variation of the impact of La Niña on the winter Arctic stratosphere - Shuangyan Yang; Tim Li; Jinggao Hu; Xi Shen (Advances in Atmospheric Sciences, 2017)

Roles of convective heating and boundary-layer moisture asymmetry in slowing down the convectively coupled Kelvin waves - Lu Wang; Tim Li (Climate Dynamics, 2017)

A special MJO event with a double Kelvin wave structure - Lili Zhu; Tim Li (Journal of Meteorological Research, 2017)

Empirical prediction of the onset dates of South China Sea summer monsoon - Zhiwei Zhu; Tim Li (Climate Dynamics, 2017)

Use of stable isotopes to understand food webs in Macao wetlands - Qian Chen; Yang Liu; Wei-Tim Ho; Shek Kiu Chan; Qiu-hua Li; Jian-Rong Huang (Wetlands Ecology and Management, 2017)

Convectively coupled Kelvin waves in CMIP5 coupled climate models - Lu Wang; Tim Li (Climate Dynamics, 2017)

Relative roles of differential SST warming, uniform SST warming and land surface warming in determining the Walker circulation changes under global warming - Lei Zhang; Tim Li (Climate Dynamics, 2017)

The statistical extended-range (10–30-day) forecast of summer rainfall anomalies over the entire China - Zhiwei Zhu; Tim Li (Climate Dynamics, 2017)

Vertex- and atlas-based comparisons in measures of cortical thickness, gyrification and white matter volume between humans and chimpanzees - William D. Hopkins; Xiang Li; Tim Crow; Neil Roberts (Brain Structure and Function, 2017)

Influence of climate regime shift on the interdecadal change in tropical cyclone activity over the Pacific Basin during the middle to late 1990s - Chi-Cherng Hong; Yi-Kai Wu; Tim Li (Climate Dynamics, 2016)

Intraseasonal variability of air temperature over the mid-high latitude Eurasia in boreal winter - Shuangyan Yang; Tim Li (Climate Dynamics, 2016)

Simulations of tropical cyclogenesis associated with different monsoon trough patterns over the western North Pacific - Xi Cao; Guanghua Chen; Tim Li; Fumin Ren (Meteorology and Atmospheric Physics, 2016)

Distinctive precursory air–sea signals between regular and super El Niños - Lin Chen; Tim Li; Swadhin K. Behera; Takeshi Doi (Advances in Atmospheric Sciences, 2016)

Factors controlling the interannual variations of MJO intensity - Li Deng; Tim Li; Jia Liu; Melinda Peng (Journal of Meteorological Research, 2016)

What controls early or late onset of tropical North Atlantic hurricane season? - Heng Zuo; Tim Li; Jia Liu; Melinda Peng (Journal of Meteorological Research, 2016)

Interannual variability of the Asian subtropical westerly jet in boreal summer and associated with circulation and SST anomalies - Yin Du; Tim Li; Zhiqing Xie; Zhiwei Zhu (Climate Dynamics, 2016)

Effects of tropical North Atlantic SST on tropical cyclone genesis in the western North Pacific - Jinhua Yu; Tim Li; Zhemin Tan; Zhiwei Zhu (Climate Dynamics, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Best practice BioBanking of human heart tissue - Sean Lal; Amy Li; David Allen; Paul D. Allen; Paul Bannon; Tim Cartmill; Roger Cooke; Alan Farnsworth; Anne Keogh; Cristobal dos Remedios (Biophysical Reviews, 2015)

Trend analysis of tropical intraseasonal oscillations in the summer and winter during 1982–2009 - Li Tao; Jiuwei Zhao; Tim Li (International Journal of Climatology, 2015)
Based on the daily outgoing long‐wave radiation data of the National Oceanic and Atmospheric Administration from 1979 to 2012, we investigated the intensity changes of the 20‐ to 70‐day boreal summer (June–September, JJAS ) intraseasonal oscillation ( BSISO ) and winter (December–February, DJF ) intraseasonal oscillation, also known as the Madden–Julian Oscillation ( MJO ). The results showed that the intensity of the BSISO has a significant intensifying trend during 1982–2009. On the other hand, little trend was found for boreal winter MJO during this period. The wavenumber‐frequency analysis was applied to separate ISO into westward propagation and eastward propagation parts. The significant intensified trend was observed over tropical Indian Ocean for the eastward propagation BSISO . The weakened but not significant trend was observed over southern tropical Indian Ocean for the eastward propagation MJO . To gain insight into the different ISO characteristics, the tendencies of sea surface temperature ( SST ) and the vertical shear of zonal wind were analysed. The results showed that in both seasons from 1982 to 2009, the global SST trends were similar, and thus they could not be used to explain the BSISO upward trend. However, lower tropospheric easterly shear in boreal summer over tropical Indian Ocean had a decreasing trend, while the easterly vertical shear over maritime continent was enhanced in winter. It is proposed that the reduced easterly vertical shear over tropical Indian Ocean favoured the amplification of the eastward propagating Kelvin wave, which led to the intensified eastward propagating BSISO . The enhanced easterly vertical shear over maritime continent might be unfavourable to the amplification of the eastward propagating Kelvin wave, but its impact was offset by the enhanced upward motion over maritime continent. As a result, there was little trend of the MJO in boreal winter. The above hypothesis was further verified by intermediate model results.

Effect of high-frequency wind on intraseasonal SST variabilities over the mid-latitude North Pacific region during boreal summer - Lu Wang; Tim Li; Tianjun Zhou (Climate Dynamics, 2015)

Strengthening of the Walker circulation under globalwarming in an aqua-planet general circulation model simulation - Tim Li; Lei Zhang; Hiroyuki Murakami (Advances in Atmospheric Sciences, 2015)

Precursor synoptic‐scale disturbances associated with tropical cyclogenesis in the South China Sea during 2000–2011 - Jinnan Yuan; Tim Li; Dongxiao Wang (International Journal of Climatology, 2015)

Three-type MJO initiation processes over the Western Equatorial Indian Ocean - Shuangli Mei; Tim Li; Wen Chen (Advances in Atmospheric Sciences, 2015)

A spatial–temporal projection model for extended-range forecast in the tropics - Zhiwei Zhu; Tim Li; Pang-chi Hsu; Jinhai He (Climate Dynamics, 2015)

Pre-treatment of remanufacturing cleaning by use of supercritical CO2 in comparison with thermal cleaning - Mingzheng Li; Weiwei Liu; Tim Short; Xiaochuan Qing; Yazhou Dong; Yanming He; Hong-Chao Zhang (Clean Technologies and Environmental Policy, 2015)

Sensitivity of the warm core of tropical cyclones to solar radiation - Xuyang Ge; Yue Ma; Shunwu Zhou; Tim Li (Advances in Atmospheric Sciences, 2015)

A spatial–temporal projection model for 10–30 day rainfall forecast in South China - Pang-Chi Hsu; Tim Li; Lijun You; Jianyun Gao; Hong-Li Ren (Climate Dynamics, 2015)

Relationship between summer rainfall anomalies and sub-seasonal oscillations in South China - Chunhui Li; Tim Li; Ailan Lin; Dejun Gu; Bin Zheng (Climate Dynamics, 2015)

Rapid assessment of fisheries species sensitivity to climate change - Gretta T. Pecl; Tim M. Ward; Zoë A. Doubleday; Steven Clarke; Jemery Day; Cameron Dixon; Stewart Frusher; Philip Gibbs; Alistair J. Hobday; Neil Hutchinson; Sarah Jennings; Keith Jones; et al. (Climatic Change, 2014)

Effect of baroclinicity on vortex axisymmetrization. Part II: Baroclinic basic vortex - Jiayi Peng; Melinda S. Peng; Tim Li; Eric Hendricks (Advances in Atmospheric Sciences, 2014)

Impacts of the diurnal cycle of radiation on tropical cyclone intensification and structure - Xuyang Ge; Yue Ma; Shunwu Zhou; Tim Li (Advances in Atmospheric Sciences, 2014)

Effect of baroclinicity on vortex axisymmetrization. Part I: Barotropic basic vortex - Melinda S. Peng; Jiayi Peng; Tim Li; Eric Hendricks (Advances in Atmospheric Sciences, 2014)

Cause of severe droughts in Southwest China during 1951–2010 - Lin Feng; Tim Li; Weidong Yu (Climate Dynamics, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Impact of Indian summer monsoon on the South Asian High and its influence on summer rainfall over China - Wei Wei; Renhe Zhang; Min Wen; Xinyao Rong; Tim Li (Climate Dynamics, 2014)

The climate regime shift over the Pacific during 1996/1997 - Chi-Cherng Hong; Yi-Kai Wu; Tim Li; Chih-Chun Chang (Climate Dynamics, 2014)

Frequency modulation of large oscillatory neural networks - Francis wyffels; Jiwen Li; Tim Waegeman; Benjamin Schrauwen; Herbert Jaeger (Biological Cybernetics, 2014)

ENSO-phase dependent TD and MRG wave activity in the western North Pacific - Liang Wu; Zhiping Wen; Tim Li; Ronghui Huang (Climate Dynamics, 2014)

Comparison of Dilute Acid and Sulfite Pretreatment for Enzymatic Saccharification of Earlywood and Latewood of Douglas fir - Chao Zhang; Xiaochun Lei; C. Tim Scott; J.Y. Zhu; Kecheng Li (BioEnergy Research, 2014)

Consequences of the Thermal Transient on the Evolution of the Damaged Zone Around a Repository for Heat-Emitting High-Level Radioactive Waste in a Clay Formation: a Performance Assessment Perspective - Li Yu; Eef Weetjens; Xavier Sillen; Tim Vietor; Xiangling Li; Pierre Delage; Vincent Labiouse; Robert Charlier (Rock Mechanics and Rock Engineering, 2014)

The intraseasonal oscillations of precipitation and circulations from January to March in 2010 in East Asia - Suxiang Yao; Qian Huang; Tim Li; Chunying Zhang (Meteorology and Atmospheric Physics, 2014)

Genome-wide association analysis for nine agronomic traits in maize under well-watered and water-stressed conditions - Yadong Xue; Marilyn L. Warburton; Mark Sawkins; Xuehai Zhang; Tim Setter; Yunbi Xu; Pichet Grudloyma; James Gethi; Jean-Marcel Ribaut; Wanchen Li; Xiaobo Zhang; Yonglian Zheng; et al. (Theoretical and Applied Genetics, 2013)

Synthesis, characterization, and biological studies of emissive rhenium–glutamine conjugates - Rachel Huang; Graeme Langille; Ravanjir K. Gill; Cindy Mei Jin Li; Yuji Mikata; May Q. Wong; Donald T. Yapp; Tim Storr (JBIC Journal of Biological Inorganic Chemistry, 2013)

MJO change with A1B global warming estimated by the 40-km ECHAM5 - Ping Liu; Tim Li; Bin Wang; Minghua Zhang; Jing-jia Luo; Yukio Masumoto; Xiaocong Wang; Erich Roeckner (Climate Dynamics, 2013)

Annual sea surface temperature lag as an indicator of regional climate variability - Chung‐Leong Li; John A.T. Bye; Stephen J. Gallagher; Tim Cowan (International Journal of Climatology, 2013)
The annual SST lag for the world ocean is obtained from a Fourier analysis of the HadISST (1870–2008) and NOAA WOA05 (1900–2005) monthly SST data series. The main properties are a mean of 73 days and a standard deviation of 16 days, with tongues of high SST lag extending poleward and eastward from the equatorial regions where a maximum in lag of about 110 days occurs. The SST lag is the sum of an atmospheric surface heat flux lag and an ocean heat storage lag which is the dominant contributor and provides direct estimates of the damping time for air/sea heat exchange, which are in good agreement with observations in the eastern North Atlantic Ocean, and also predictions of the phase lag of the mid‐latitude ocean surface temperature field to El Nino‐Southern Oscillation (ENSO) forcing. Hence, SST lag can be used to diagnose global climate variability. Local differences in lag of up to about 15 days occur between the 1991–2005 and 1976–1990 periods, which are accompanied by significant changes in regional climate. The lag time series for grid points in the eastern Indian Ocean, North Pacific Ocean and North Atlantic Ocean show that the variability can be interpreted in terms of bounded random walks of length about 20 years. The CSIRO Mk. 3.5 run for Scenario A2 over the period 1871–2100 has a similar random structure and also shows a secular increase in SST lag in the temperate oceans which is attributable to an expansion of the tropical belt.

A new paradigm for the predominance of standing Central Pacific Warming after the late 1990s - Baoqiang Xiang; Bin Wang; Tim Li (Climate Dynamics, 2013)

Structures and mechanisms of the first-branch northward-propagating intraseasonal oscillation over the tropical Indian Ocean - Kuiping Li; Weidong Yu; Tim Li; V. S. N. Murty; Somkiat Khokiattiwong; T. R. Adi; S. Budi (Climate Dynamics, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Interannual variation of multiple tropical cyclone events in the western North Pacific - Jianyun Gao; Tim Li (Advances in Atmospheric Sciences, 2012)

Effects of air–sea coupling on the boreal summer intraseasonal oscillations over the tropical Indian Ocean - Ailan Lin; Tim Li; Xiouhua Fu; Jing-Jia Luo; Yukio Masumoto (Climate Dynamics, 2011)

A rapid detection method for apoptosis and necrosis measurement using the Cellometer imaging cytometry - Leo Li-Ying Chan; Ning Lai; Elena Wang; Tim Smith; Xifeng Yang; Bo Lin (Apoptosis, 2011)

Identification and Characterization of a Multigene Family Encoding Germin-Like Proteins in Cultivated Peanut (Arachis hypogaea L.) - Xiaoping Chen; Ming Li Wang; Corley Holbrook; Albert Culbreath; Xuanqiang Liang; Tim Brenneman; Baozhu Guo (Plant Molecular Biology Reporter, 2011)

Projection of future precipitation change over China with a high-resolution global atmospheric model - Lei Feng; Tianjun Zhou; Bo Wu; Tim Li; Jing-Jia Luo (Advances in Atmospheric Sciences, 2011)

The Kabanga Ni sulfide deposit, Tanzania: I. Geology, petrography, silicate rock geochemistry, and sulfur and oxygen isotopes - Wolfgang D. Maier; Sarah-Jane Barnes; Arindam Sarkar; Ed Ripley; Chusi Li; Tim Livesey (Mineralium Deposita, 2010)

A Serial Analysis of Gene Expression Profile of the Alzheimer’s Disease Tg2576 Mouse Model - Amee J. George; Lavinia Gordon; Tim Beissbarth; Irene Koukoulas; R. M. Damian Holsinger; Victoria Perreau; Roberto Cappai; Seong-Seng Tan; Colin L. Masters; Hamish S. Scott; Qiao-Xin Li (Neurotoxicity Research, 2010)

SAGE Analysis of Genes Differentially Expressed in Presymptomatic TgSOD1G93A Transgenic Mice Identified Cellular Processes Involved in Early Stage of ALS Pathology - Michel Guipponi; Qiao-Xin Li; Lavinia Hyde; Tim Beissbarth; Gordon K. Smyth; Colin L. Masters; Hamish S. Scott (Journal of Molecular Neuroscience, 2010)

Immunogenicity and efficacy of a bacterially expressed HEV ORF3 peptide, assessed by experimental infection of primates - Hongxia Ma; Xiaoguo Song; Tim J. Harrison; Rongcheng Li; Guoyong Huang; Heqiu Zhang; Wei Kong; Youchun Wang (Archives of Virology, 2009)

Degradation of benzo(a)pyrene in Yangtze River source water with functional strains - Yan Zhang; Xuxiang Zhang; Bing Wu; Dayong Zhao; Mei Li; Yibin Cui; Tim Ford; Shupei Cheng (Ecotoxicology, 2009)

Impact of El Niño onset timing on the Indian Ocean: Pacific coupling and subsequent El Niño evolution - K. P. Sooraj; Jong-Seong Kug; Tim Li; In-Sik Kang (Theoretical and Applied Climatology, 2009)

Interactions between the tropical ISO and midlatitude low-frequency flow - Lin-Lin Pan; Tim Li (Climate Dynamics, 2008)

Computerized methods of analyzing faults between wells - Zhou Xiaojun; Xue Linfu; Dai Liming; Li Sanzhong; Tim Kusky (Applied Geophysics, 2006)

Safety of intravenous methamphetamine administration during treatment with bupropion - Thomas F. Newton; John D. Roache; Richard De La Garza; Tim Fong; Christopher L. Wallace; Shou-Hua Li; Ahmed Elkashef; Nora Chiang; Roberta Kahn (Psychopharmacology, 2005)

A GH3-like gene, CcGH3, isolated from Capsicum chinense L. fruit is regulated by auxin and ethylene* - Kede Liu; Byoung-Cheorl Kang; Hui Jiang; Shanna L. Moore; Hanxia Li; Christopher B. Watkins; Tim L. Setter; Molly M. Jahn (Plant Molecular Biology, 2005)

Phenotypic assessment of galanin overexpressing and galanin receptor R1 knockout mice in the tail suspension test for depression-related behavior - Andrew Holmes; Qian Li; Elizabeth A. Koenig; Eric Gold; Dejaimenay Stephenson; Rebecca J. Yang; Jennifer Dreiling; Tim Sullivan; Jacqueline N. Crawley (Psychopharmacology, 2005)

Digital Forestry: A White Paper - Guang Zhao; Guofan Shao; Keith M. Reynolds; Michael C. Wimberly; Tim Warner; John W. Moser; Keith Rennolls; Steen Magnussen; Michael Köhl; Hans-Erik Anderson; Guillermo A. Mendoza; Limin Dai; et al. (Journal of Forestry, 2005)
Digital Forestry has been proposed as ”the science, technology, and art of systematically acquiring, integrating, analyzing, and applying digital information to support sustainable forests.” Although rooted in traditional forestry disciplines, Digital Forestry draws from a host of other fields that, in the past few decades, have become important for implementing the concept of forest ecosystem management and the principle of sustainable forestry. Digital Forestry is a framework that links all facets of forestry information at local, national, and global levels through an organized digital network. It is anticipated that a new set of principles will be established when practicing Digital Forestry concept for the evolution of forestry education, research, and practices as the 21st century unfolds.

Estimating the Strength and Direction of Functional Coupling in the Lamprey Spinal Cord - Tim Kiemel; Kevin M. Gormley; Li Guan; Thelma L. Williams; Avis H. Cohen (Journal of Computational Neuroscience, 2003)

Inhibition of VLA-4 and up-regulation of TIMP-1 expression in B16BL6 melanoma cells transfected with MHC class I genes - Fan Xu; Tim Carlos; Mengfeng Li; Otto Sanchez-Sweatman; Rama Khokha; Elieser Gorelik (Clinical & Experimental Metastasis, 1998)

Effect of the peroxisome proliferator perfluorodecanoic acid on growth and lipid metabolism in Sprague Dawley rats fed three dietary levels of selenium - Tim Borges; Howard P. Glauert; Li -Chuan Chen; Ching K. Chow; Larry W. Robertson (Archives of Toxicology, 1990)